Process for the preparation of a powder comprising at least one polymer and such a powder

CN115943060BActive Publication Date: 2026-10-09EOS GMBH ELECTRO OPTICAL SYST
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN201980028189.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-04-23
Filing Date
2019-04-23
Publication Date
2026-10-09
Estimated Expiration
2039-04-23

AI Technical Summary

Benefits of technology

[0352] The inventors have recognized that, in combination with the above-mentioned advantages possible according to the invention, it is important to apply high shear energy to the powder in the shortest possible time without overheating the powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115943060B_ABST
    Figure CN115943060B_ABST
Patent Text Reader

Abstract

A process for the preparation of a powder comprising at least one polymer for use in an additive manufacturing process of a three-dimensional object is described, comprising the step of mechanically treating the powder with at least one rotating mixing blade in a mixer, wherein the powder is exposed to a temperature T B , wherein if the polymer is a semi-crystalline polymer, T B is at least 30°C and wherein T B is below the melting point T m of the polymer (determined according to DIN EN ISO 11357), or wherein if the polymer is a melt amorphous polymer, T B is at least 30°C and wherein T B is at most 50°C above the glass transition temperature T g of the polymer (determined according to DIN EN ISO 11357). At least a 10% increase in the bulk density (or at least a 2% increase in the case of a polymer, copolymer or polymer blend of a polyamide) and at least a 10% decrease in the BET surface area and optionally also an improvement in the fluidization ability by at least 10% of the powder can be achieved after the treatment compared to the time before the treatment started.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention relates to a method for preparing powders comprising at least one polymer for use in additive manufacturing methods of three-dimensional objects, and to corresponding powders.

[0002] Additive manufacturing methods for three-dimensional objects by selectively solidifying powdered materials layer by layer are used in, for example, rapid prototyping, rapid machining, and additive manufacturing. Examples of such methods are known as "selective laser sintering" or "selective laser melting." Here, thin layers of powdered material (the so-called "build material") are repeatedly applied within a build area, and the powdered material in each layer is selectively solidified by selective irradiation with a laser beam. This means that the powdered material partially or completely melts and solidifies at these locations to form a material bond. In this way, a three-dimensional object is produced. Powdered materials containing polymers can be used here.

[0003] For example, document DE 195 14 740 C1 describes a method for manufacturing three-dimensional objects by selective laser sintering and an apparatus for carrying out the method.

[0004] Document EP 2 123 430 A1 describes a method for manufacturing three-dimensional objects by selectively sintering powders using electromagnetic radiation, such as laser radiation. The powders contain polymers or copolymers derived from polyaryletherketones (PAEKs).

[0005] When fabricating three-dimensional objects using one of the known methods by selectively solidifying powdered materials layer by layer, the challenge lies in producing three-dimensional objects with sufficient precision, i.e., high dimensional accuracy. Another challenge is to specifically impart the desired material properties to the three-dimensional objects fabricated in this way.

[0006] In particular, it is generally desirable to manufacture three-dimensional objects with the lowest possible porosity, because the lower the porosity of a three-dimensional object, the more favorable its mechanical properties (tensile strength, E-modulus, elongation at break, toughness, impact strength, etc.) are.

[0007] If three-dimensional objects are prepared, for example, by selective laser sintering or selective laser melting, many powders, after being prepared through polymerization and optionally subsequent pulverization, result in three-dimensional objects with high porosity and generally unfavorable mechanical properties. Furthermore, in the case of selective laser sintering, these powders are often only insufficiently metered and applied as a powder layer. The result can be process instability (insufficient metering) and inhomogeneous coatings in the powder bed. Inhomogeneous coatings can, in turn, lead to an additional increase in the porosity of the three-dimensional object and thus result in poor mechanical properties.

[0008] The aforementioned problems occur particularly frequently if the powder used contains thermoplastic polymers.

[0009] Various methods are known in the prior art for pulverizing polymer materials to obtain powders, such as solvent precipitation, grinding, especially cryogenic grinding of coarse powder or granules, melt spraying, spray drying, melt dispersion, and melt spinning, wherein melt spinning includes a fiber cutting step. In principle, polymers can also exist as powders after polymerization without requiring a separate pulverization step.

[0010] The object of this invention is to provide an improved method for preparing powders, wherein the powders comprise at least one polymer and wherein the powders are intended for use in additive manufacturing methods for three-dimensional objects. Particularly preferred is a method for preparing powders that can be used to fabricate three-dimensional objects with improved properties such as lower porosity, higher transparency, better dimensional stability, and / or better shape fidelity, without compromising mechanical properties.

[0011] Another object of the present invention is to provide a suitable powder. This object is achieved by the method according to claim 1, the method according to claim 9, and the powder according to claims 14 and 16. Accordingly, an additive manufacturing method for preparing three-dimensional objects is provided according to claim 18.

[0012] Pretreatment of initial polymer powders has been attempted prior to actual methods of fabricating three-dimensional objects in order to influence porosity (or BET surface area) or bulk density. For example, WO2004 / 050746 A (EP1537170B) describes heating polyamide 12 powder obtained by precipitation to 140°C in a commercially available mixer for 10 minutes, then holding it at that temperature for five minutes to reduce the BET surface area. Example 7 in WO2008 / 122426 describes a treatment to increase bulk density, wherein PEEK powder is heated to 150°C for 25 minutes in a commercially available mixer, then held at that temperature for 25 minutes, then further heated to 170°C for 20 minutes, and finally held at 170°C for 60 minutes. US 2017 / 0312938 A1 discloses pretreatment of PEKK powder with a mixer equipped with rotor blades (30 to 120 minutes; rotor speed 30 to 70 m / s). At a rotor blade speed of 43 m / s, an increase in tap density of the treated PEKK powder was demonstrated. However, prior art literature does not show how tap density and BET surface area are simultaneously improved in a material-specific manner, and how they are improved to improve the powder's performance in terms of lower porosity, excellent dimensional stability, and / or better shape retention for three-dimensional objects manufactured from this material, without compromising mechanical properties, with a low renewal factor. Clearly, by means of the pretreatment method according to the invention, taking into account the key polymer material-related temperature parameters disclosed herein, and, if applicable, other relevant processing conditions also disclosed herein, it is possible to achieve, to date, a fine surface structure and even surface rounding in the microscopic surface regions of each polymer particle, while simultaneously ensuring excellent particle size distribution of the polymer powder, wherein the reduction in bulk density and the increase in BET surface area are good indicators of the improved surface structure and rounding—BET is increased not only in absolute values ​​but, in particular, as a relative percentage compared to the corresponding starting material, independent of the preparation method of the starting material.

[0013] The features defined in the dependent claims and the features expressed in the specification constitute a further development of the solution principle defined in the independent claims, and further contribute to achieving the surprising effects and unexpected advantages described below.

[0014] Features in the dependent claims and features in the portion of the specification relating to one of these methods are also further developments of other methods and powders, and vice versa.

[0015] In order to measure the temperature that occurs during the process of the method of the present invention (T according to the definition given below) max and T ManPreferably, temperature sensors are used, which automatically record the temperature or transmit it to a control device. These temperature sensors are preferably arranged inside the mixer or in the mixer's jacket, so that they can record the temperature of the mixture or the jacket. The temperature sensors may be, for example, temperature sensors comprising thermocouples and / or measuring resistors, preferably having a measurement accuracy of 1°C, more preferably 0.1°C, or even higher, over a relevant temperature range from room temperature to several hundred degrees Celsius. The corresponding temperature sensors have already been integrated by the manufacturer into commercially available mixers.

[0016] If reference is made to the following description and claims regarding the thermal flexural temperatures HDT-A or HDT-B, these are values ​​determined according to the relevant standard DIN EN ISO 75 (Parts 1-3).

[0017] In the context of this invention, HDT-A and HDT-B values ​​refer to the polymer itself. The following applies to polymeric materials composed of a matrix consisting of a specific polymer in which additives, such as reinforcing materials, are embedded: the HDT-A and HDT-B values ​​of the polymeric material are defined as the HDT-A and HDT-B values ​​of the polymer constituting the matrix, respectively. This also applies if different thermal flexural temperatures of the polymeric material are actually measured according to DIN EN ISO 75. PEKK-60 / 40, for example, has an HDT-A value of 139°C. The thermal flexural temperature is increased by adding carbon fibers as a reinforcing material. However, in the context of this invention, the HDT-A value of carbon fiber reinforced PEEK-60 / 40 is 139°C.

[0018] For the purposes of this invention, it has been found that the selection of powder temperature during the mechanical processing in the mixer is, in fact, or at least substantially, not dependent on whether the powder is reinforced with fibrous materials or another additive, or whether the powder has been pretreated, for example, by heating. The temperature characteristics of the polymer itself (HDT-A, HDT-B, glass transition temperature TB) are also relevant. g Melting point T m This is necessary. This indicates that there is a theory regarding the modification of the powder particle surface, particularly rounding and / or smoothing, during the process according to the method of the invention. The thermal or mechanical energy required for such surface modification provided by the invention depends not or only slightly on whether the powder particles are reinforced in the bulk (i.e., within the particles).

[0019] PEKK-60 / 40 is a polyetherketone ketone with a terephthalic acid / isophthalic acid isomer ratio of 60 / 40, meaning the molar fraction of terephthalic acid is 60%. Therefore, PEKK-70 / 30 and PEKK-80 / 20 are polyetherketone ketones with terephthalic acid / isophthalic acid isomer ratios of 70 / 30 and 80 / 20, respectively.

[0020] Table 1 provides examples of HDT-A and HDT-B values ​​for various polymers (each of which may be taken from the literature or determined according to DIN EN ISO 75), some of which are used in the examples described below. Common abbreviations for the polymers are used. Table 1 also gives the glass transition temperatures Ti for these polymers. g (Determined according to DIN EN ISO 11357) and melting point T m (According to DIN EN ISO 11357) value. If “nm” is given in a table field instead of a value, it means that no corresponding value is available or cannot be determined.

[0021] Table 1

[0022]

[0023]

[0024] In the context of this invention, the glass transition temperature T of the material used g and melting point T m The measurements were performed according to standard DIN ENISO 11357 by DSC. Measurements were conducted on a "Mettler Toledo DSC823e" DSC apparatus equipped with an automatic sample changer. Evaluation was performed using "STARe software" version 9.30. Nitrogen gas, 5.0 g (99.999% by volume) of purity, was used as the purge gas. A sufficiently wide temperature range was examined for each material using DSC (for the PEKK material examined, e.g., 0°C–360°C). The heating and cooling rates were 20°C / min. The melting point was determined during the first heating run. The melting point corresponds to the peak temperature.

[0025] In the context of this invention, polymers in which no crystallization or no crystallization is observed in DSC measurements at a cooling rate of 20°C / min are referred to as molten amorphous polymers.

[0026] In the context of this invention, polymers referred to as pseudo-amorphous polymers are those that, according to DIN EN ISO 11357, exhibit at least one melting peak during a first heating run measured by DSC at a heating rate of 20 °C / min, but show substantially no crystallization when cooled at a cooling rate of 20 °C / min. Pseudo-amorphous polymers may behave like amorphous and / or like semi-crystalline materials.

[0027] In the context of this invention, when the powder contains polyether ketone ketone (PEKK), particle size and their distribution are determined by laser diffraction according to standard ISO 13320. Measurements are performed in water with a dispersion medium (surfactant) added, using a CILAS 1064 instrument with a wet dispersion cell from Quantachrome Partikelmesstechnik. During the wet dispersion process, the sample is further dispersed ultrasonically. The particle size distribution is evaluated according to the Fraunhofer model.

[0028] In the case of residual powder, particle size and their distribution were determined optically according to ISO 13322-2. Here, the sample was dispersed in a liquid medium. The liquid medium was pumped so that it flowed along the front of a calibrated optical unit. For evaluation, 10,000 individual images were taken. Particle size and shape were determined according to defined measurement parameters. The determined size is a measure of particle size having an area equal to the area of ​​a circle projected onto the particle. Ai The diameter (denoted as d) 10 d 50 and d 90 These are represented as the 10%, 50%, and 90% quantiles of the volumetric particle size distribution. In the context of this invention, details of the quantiles and the values ​​calculated therefrom relate to the mentioned method. Ultrafine particles (with X...) were also measured. Ai <10M m The volume fraction of particles. This volume fraction is referred to below as the "ultrafine powder fraction".

[0029] From the quantities measured as described above, the distribution width VB of the particle size distribution can be calculated using the following formula:

[0030] VB = (d 90 -d 10 ) / d 50

[0031] For the optical method, distilled water was placed in the receiving vessel of a Camsizer XT measuring device (Retsch Technology, software version 6.0.3.1008) equipped with an X-flow module and degassed. The surface density of the particles / bubbles being measured was less than 0.01. Approximately 1 to 3 mg of the powdered material to be analyzed was dispersed in 2 to 3 mL of a Triton X aqueous solution. The concentration of Triton X in the solution was 3% by mass. The dispersed sample was slowly added dropwise to the distilled water in the receiving vessel until a surface density of 0.4 to 0.6 was reached. Measurements were initiated and repeated several times to obtain statistical measurements.

[0032] The rotational speed of the mixer is given as the speed of the mixing blades at the ends furthest from the drive shaft of the mixer. In the context of this invention, this rotational speed of the mixer is also referred to as "mixer speed," "mixing blade speed," or "mixing blade rate."

[0033] By using velocity data, such as in m / s, the mixing speed, which is independent of the size of the mixer, can be measured, and thus the energy introduced into the material (powder) to be mixed through the mixing process can be measured.

[0034] Fluidization capacity was determined using a 25 mm nozzle as a test funnel according to ISO 6186 standard.

[0035] BET surface area was determined by nitrogen adsorption according to DIN ISO 9277. Measurements were performed using Quantachrome Instruments v11.0 software on a measuring apparatus at Quantachrome, NovaStation A. Prior to measurement, the sample was degassed at 80°C under a vacuum of approximately 100 mbar for 2 hours. Evaluation was performed using a 5-point method.

[0036] The present invention also discloses and defines the following embodiments or projects.

[0037] 1. A method for preparing a powder comprising at least one polymer for use in an additive manufacturing method of a three-dimensional object.

[0038] Includes the step of mechanically processing the powder in a mixer using at least one rotating mixing blade.

[0039] The powder is exposed to temperature T B ,

[0040] If the polymer is a semi-crystalline polymer, then T B At least 30°C and below the polymer's melting point T m (Measured according to DIN EN ISO 11357), or

[0041] If the polymer is a molten amorphous polymer, then T B For at least 30°C and above the polymer's glass transition temperature T g At most 50°C, preferably at most 30°C, more preferably at most 20°C, and particularly preferably at most 10°C (as determined according to DIN EN ISO 11357).

[0042] 2. According to the method in Project 1, where T B By one or more of the following conditions or methods (i) to (iv):

[0043] (i) Optionally, if the polymer is a semi-crystalline polymer, then TB Greater than the polymer’s thermal flexural temperature HDT-A (determined according to DIN EN ISO 75; measured in standard determination on specimens consisting only of polymer, i.e., without any additives, especially without fillers or reinforcing materials; the prepared specimens are preferably without post-treatment, especially without tempering);

[0044] (ii) Optionally, if the polymer is a semi-crystalline polymer, especially if the polymer is a molten amorphous polymer, then T B Below the glass transition temperature T of the polymer g Up to 100°C, preferably down to 50°C, particularly preferably down to 20°C (as determined according to DIN EN ISO 11357);

[0045] (iii) For the polymer powder to be used, T B At most, the temperature Tmax is the temperature determined in a temperature-current consumption measurement of the same polymer in a mixer with mixing blades rotating in the range of 20 to 50 m / s during heating, preferably under mixing conditions where the maximum allowable heating phase is less than 60 minutes, wherein Tmax is determined in a standard temperature-current consumption measurement by one or both of the following methods (a) or (b):

[0046] (a) Determining the maximum T using a temperature-current consumption graph B One data point is recorded every minute, wherein only those [(gradient / min) / current consumption] within the range of Tg-20℃ to Tm are considered to be at least greater than 5% and at most 30%, preferably greater than 7% and less than 20%, more preferably greater than 9% and less than 15%, particularly greater than 12%; or

[0047] (b) Maximum T B The current consumption of the mixer is determined by a temperature-current consumption graph, wherein the current consumption of the mixer increases disproportionately and strongly to an increased current consumption value lx within a short period of time, which is at least 10%, preferably at least 20%, more preferably at least 50% and / or at most 100% higher than the average of 10 previous measurement points, with at least one measurement recorded per minute, wherein only the current increase in the range of Tg-20°C to Tm is considered; regarding (iii), it is irrelevant if the current consumption decreases again after the aforementioned increase occurs;

[0048] (iv)T B The maximum Tmax is the temperature at which the bulk density of the powder decreases to less than the bulk density of the untreated powder when the mixer is used (±10°C), preferably at least 1%, more preferably at least 2%, more preferably at least 3%, particularly at least 5%, or all greater than at least 10% of the maximum bulk density of the treated powder, wherein the maximum Tmax is determined by using different T... BHowever, in a series of tests conducted under otherwise identical mixing conditions, preferably by means of a mixer rotation speed in the range of 20 to 50 m / s during the heating phase followed by the same residence time, for example, a residence time of 0 to 10 minutes, preferably within a range allowing for variations in T... B Under mixed conditions with a maximum test duration of 60 minutes.

[0049] 3. According to the method of Project 1 or 2, where a semi-crystalline polymer is used, particularly polyamide or polyaryletherketone (PAEK), wherein in this case T B Below the crystallization point Tk (determined according to DIN EN ISO 11357 at a cooling rate of 20 °C / min).

[0050] 4. The method according to item 1 or 2, wherein a pseudo-amorphous polymer is used, particularly a pseudo-amorphous polycarbonate, a pseudo-amorphous polyetherimide, or a pseudo-amorphous polyether ketone ketone, or copolymers or polymer blends thereof, especially having the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at most 80%, preferably at most 60%, and / or at least 40% of the polyether ketone ketone, wherein in this case T B The temperature is at most 40°C above the Tg of the polymer.

[0051] 5. According to the method of Project 1 or 2, wherein a molten amorphous polymer, particularly polystyrene, is used, wherein in this case T B The temperature is at most 20°C above the Tg, preferably at most 10°C above the Tg, or optionally below the Tg of the polymer.

[0052] 6. The method according to one of the preceding projects, wherein the rotational speed of the mixer is adjusted to adjust the temperature T of the powder exposure. B Temperature T is achieved, arbitrarily, solely by the mixer's rotational speed and by the processing time. B The adjustment.

[0053] 7. The method according to one of the preceding projects, wherein the powder is supplied substantially by mechanical processing or solely by mechanical processing to reach and / or maintain a temperature T. B The heat energy.

[0054] 8. Based on one of the methods in the aforementioned project,

[0055] Among them, reaching T B Previously, during the heating process, the rotational speed of the mixer was at least 100 rpm, preferably at least 1000 rpm, and particularly preferably at least 2000 rpm.

[0056] 9. Based on one of the methods in the aforementioned project,

[0057] During the heating process prior to reaching TB, the rotational speed of the mixer is at most 10,000 rpm, preferably at most 5,000 rpm, and particularly preferably at least 3,000 rpm.

[0058] Advantageously, the first condition applies to mixers with a relatively large volume (e.g., greater than 40 liters), while the second condition applies to mixers with a relatively small volume (e.g., at most 40 liters); thus adjusting the corresponding energy input.

[0059] 10. Based on the method of one of the aforementioned projects,

[0060] Among them, reaching T B Previously, the maximum velocity of the mixing blades during the heating process was at least 20 m / s, preferably at least 30 m / s, particularly preferably at least 35 m / s, and / or

[0061] Among them, reaching T B Previously, the maximum speed during the heating process was at most 100 m / s, preferably at most 70 m / s, and particularly preferably at most 50 m / s.

[0062] Among them, in T B In the range below 100°C, when T is reached B Previously, during the heating stage, the maximum speed of the mixing blades was at most 20 m / s, preferably in the range of 8 to 14 m / s.

[0063] Advantageously, the first condition applies to mixers with relatively large volumes (e.g., greater than 40 liters), while the second condition applies to mixers with relatively small volumes (e.g., at most 40 liters); thus adjusting the appropriate energy input accordingly.

[0064] During the holding phase, the maximum speed of the mixing blades can be at least 20 and / or at most 100 m / s, preferably at least 30 and / or at most 70 m / s, and particularly at least 35 and / or at most 50 m / s. If the processing temperature is below 100°C, the maximum speed of the mixing blades during the heating phase should be in the range of 5 to 15 m / s, preferably in the range of 8 to 12 m / s.

[0065] The rotary mixer process according to the invention preferably includes only a heating phase / heating time and a holding phase / dwell time, and does not include any additional heating phase / heating time of the rotary mixer. However, optionally, for example when using PAEK powder, an additional pure heating step may be added without use or with very few cycles.

[0066] 11. Based on the method of one of the aforementioned projects,

[0067] At least a portion of the powder was from below T B And in particular, the initial temperature of at least room temperature and / or at most 60°C above room temperature is reached within a heating time of 20 minutes, preferably within 15 minutes, more preferably within 10 minutes, and still more preferably within 5 minutes. B .

[0068] 12. Based on one of the methods in the aforementioned project,

[0069] Among them, reaching T B After that, the temperature was maintained at T. B ±20℃, preferred T B ±10℃, specially selected T B The duration of residence within the range of ±5℃.

[0070] 13. According to the method in Project 12,

[0071] The dwell time is at most 90 minutes, preferably at most 60 minutes, more preferably at most 30 minutes, particularly preferably at most 20 minutes, most preferably at most 12 minutes and / or the dwell time is at least 1 minute, preferably at least 3 minutes, more preferably at least 5 minutes, and most preferably at least 10 minutes.

[0072] 14. According to one of the methods in items 12 and 13,

[0073] During the residence time, the maximum velocity of the mixing blades is at least 8 m / s, preferably at least 10 m / s, more preferably at least 20 m / s, particularly preferably at least 30 m / s, or at least 35 m / s and / or

[0074] The maximum speed during the dwell time is at most 100 m / s, preferably at most 70 m / s, and especially preferably at most 50 m / s.

[0075] 15. According to one of the methods in items 12 to 14,

[0076] Preferably, the maximum speed of the mixing blades during the residence time is at least 10% lower than the maximum speed of the mixing blades during the heating time, and more preferably at least 15% lower.

[0077] 16. Based on one of the methods in the aforementioned project,

[0078] The polymer is a semi-crystalline polymer and T is present in the polymer. B Above the thermal flexural temperature HDT-A and / or below the thermal flexural temperature HDT-B, and / or wherein the polymer is a semi-crystalline polymer and wherein T B Below the melting point T mAt least 20°C, preferably below the melting point T, especially in the case of polymers, copolymers or polymer blends of polyamides. m At least 50°C, and / or

[0079] The polymer is a semi-crystalline polymer and T is present in the polymer. B The maximum temperature is 250°C or 300°C (optional).

[0080] 17. According to the method of any one of the aforementioned projects,

[0081] Wherein the polymer is a molten amorphous polymer and where T B At most at the glass transition temperature and below the glass transition temperature T g At least 10°C, preferably at least 20°C, and / or

[0082] Wherein the polymer is a molten amorphous polymer and where T B The temperature is above the thermal flexure temperature HDT-A (as determined according to DIN EN ISO 75), preferably between the thermal flexure temperature HDT-A (as determined according to DIN EN ISO 75) and the thermal flexure temperature HDT-B (as determined according to DIN EN ISO 75).

[0083] 18. The method according to one of the preceding projects, wherein the polymer is polyetherketoneketone.

[0084] The polyetherketone ketone has the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at most 80%, preferably at most 70%, more preferably at most 65% and / or at least 20%, preferably at least 40%, more preferably at least 55%.

[0085] Where T B The temperature is at least 90°C, preferably at least 100°C, and more preferably at least 110°C.

[0086] and / or

[0087] Where T B For a maximum Tg +50℃, preferably for a maximum Tg +30℃, more preferably for a maximum Tg +10℃, and particularly preferably for a maximum Tg +50℃. g .

[0088] 19. The method according to one of the foregoing items, wherein the powder comprises polyphenylene sulfide,

[0089] And among them T B The temperature is at least 100°C and / or at most 210°C, preferably at least 150°C and / or at most 190°C, and particularly preferably at least 170°C and / or at most 180°C.

[0090] 20. Based on the method of one of the aforementioned projects,

[0091] In order to dissipate some of the heat energy supplied to the powder through mechanical processing, the mixer, especially the mixer jacket, is actively temperature-controlled or cooled to below T. B The temperature is preferably cooled by water, by another liquid coolant, and / or by thermoelectric cooling, especially by the use of a thermostat.

[0092] 21. Based on the method of one of the aforementioned projects,

[0093] At least one of the mixing blades is located in the bottom region of the mixer.

[0094] 22. Based on one of the methods in the aforementioned project,

[0095] The number of mixed blades is at least two, preferably at least three, more preferably at least four, and / or

[0096] The mixed blades are arranged around a common axis, wherein a portion of the mixed blades are optionally offset relative to another portion of the mixed blades along the axis, and / or a portion of the mixed blades are optionally twisted relative to another portion of the mixed blades, preferably twisted by 90°.

[0097] 23. Based on one of the methods in the aforementioned project,

[0098] The powder is exposed to temperature T B Subsequently, before use in the additive manufacturing process, the material is mechanically processed in a mixer or in a cooling mixer different from the mixer during the cooling process to a temperature preferably at most 35°C, the cooling mixer having at least one rotating mixing blade and preferably having a volume at least 50%, more preferably at least 100%, particularly preferably at least 110% larger than the mixer.

[0099] 24. According to the method in Project 23,

[0100] For cooling purposes, the maximum speed of the mixing blades of the mixer or cooling mixer is at most 20 m / s, preferably at most 10 m / s, wherein the mixer or cooling mixer is optionally actively cooled, particularly the jacket of the mixer or cooling mixer.

[0101] 25. According to one of the methods in items 23 and 24,

[0102] During the cooling process, additives, preferably fluidizing agents and / or fillers may be added to the powder in a mixer or cooling mixer.

[0103] 26. The method according to any one of the foregoing items further includes the additional step of exposing the powder to temperature T by heating for at least 30 minutes and / or up to 30 hours. NPreferably, no powder is moved during this time period, or the powder is moved by mechanical circulation of up to 10 r / μm, preferably in a rotary furnace.

[0104] This additional step is advantageously associated with one or more of the following conditions, each compared with the corresponding parameter value prior to this additional step: increasing bulk density, improving fluidization capacity (flowability), reducing BET, increasing the onset temperature of melting point, and / or increasing the enthalpy of fusion of the processed powder.

[0105] 27. According to the method in Project 26,

[0106] The powder contains a semi-crystalline polymer, wherein T N Preferably, it has at least a glass transition temperature T. g (as determined according to DIN ENISO 11357) and / or at most melting point T m (According to DIN EN ISO 11357).

[0107] 28. A method for preparing a powder comprising at least one polymer for use in an additive manufacturing method of a three-dimensional object.

[0108] Includes the step of mechanically processing the powder in a mixer using at least one rotating mixing blade.

[0109] The temperature T at which the powder appears is adjusted in this way compared to the time before and after the start of the process. B .

[0110] —The bulk density of the powder is increased by at least 10%, or in the case of polymers, copolymers, or polymer blends of polyamides, by at least 2%, preferably at least 4%, particularly at least 5%, and —The BET surface area of ​​the powder is reduced by at least 10%.

[0111] —Optionally, fluidization capacity is also improved by at least 10%.

[0112] 29. According to the method in Project 28,

[0113] The process conditions are applied as described in one of items 1 to 27.

[0114] 30. According to the method in Project 28,

[0115] The temperature T is regulated by adjusting the rotational speed (mixer speed) and processing time. B ,

[0116] Preferably, the temperature T is adjusted solely by regulating the mixer's rotational speed and the processing duration. B .

[0117] 31. According to one of the methods in items 28 to 30,

[0118] The polymer is amorphous or preferably semi-crystalline, and the powder reaches temperature T within no more than 25 minutes, preferably no more than 10 minutes, and more preferably no more than 5 minutes from the initial temperature. B ,

[0119] Optionally, the temperature is maintained at T by adjusting the rotational speed of the mixer. B ±20℃, preferred T B ±10℃, specially selected T B It lasts for a period of time within the range of ±5℃.

[0120] 32. According to one of the methods in items 28 to 31,

[0121] At least one of the following measures is also taken:

[0122] (a) Using at least two, preferably at least three, mixing blades in a mixer, wherein the mixing chamber of the mixer has a volume of at least 5 L and / or at most 100 L, preferably at least 20 L and / or at most 60 L, more preferably at least 30 L and / or at most 50 L;

[0123] (b) Using at least four, preferably at least five, mixing blades in a mixer, wherein the mixing chamber of the mixer has a volume of at least 200L and / or at most 1000L, preferably at least 400L and / or at most 800L, more preferably 500L-700L;

[0124] (c) Select a mixer fill level of at least 30% and / or at most 99%, preferably at least 65% and / or at most 95%, especially when using active jacket cooling.

[0125] 33. According to the method of one of items 28 to 32, wherein the polymer is polyetherketoneketone.

[0126] The polyetherketone ketone has the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at most 80%, preferably at most 70%, more preferably at most 65% and / or at least 20%, preferably at least 40%, more preferably at least 55%, and

[0127] The powder has a content of at least 0.25 g / cm³. 3 Preferably, it is at least 0.26 g / cm³. 3 More preferably at least 0.3 g / cm³ 3 Even more preferably, at least 0.35 g / cm³ 3 Preferably, it is at least 0.37 g / cm³. 3 The initial packing density.

[0128] 34. The method according to any one of items 28 to 32, wherein the powder is polyetheretherketone (PEEK) or a copolymer of it with diphenyl etherketone (PEEK-PEDEK), having a concentration of at least 0.29 g / cm³. 3 Or 0.30g / cm 3 Preferably, it is at least 0.34 g / cm³. 3 More preferably at least 0.38 g / cm³ 3 More preferably, at least 0.40 g / cm³ 3 The initial packing density.

[0129] 35. According to one of the methods in items 28 to 32,

[0130] The powder is polyphenylene sulfide, with a content of at least 0.40 g / cm³. 3 Preferably at least 0.42 g / cm³ 3 More preferably at least 0.46 g / cm³ 3 Even more preferably, at least 0.48 g / cm³ 3 The initial packing density.

[0131] 36. According to one of the methods in items 28 to 35,

[0132] The bulk density of the powder is increased by at least 15%, preferably at least 20%, more preferably at least 25%, and even more preferably at least 30%, and / or

[0133] The BET surface area of ​​the powder is reduced by at least 20%, preferably at least 30%, more preferably at least 40%, and even more preferably at least 60%.

[0134] 37. The method according to any one of items 28 to 36, wherein the fine powder content is reduced by at least 5%, preferably at least 10%, more preferably at least 20%, or even more preferably at least 20%, after treatment compared to the time point before the start of treatment.

[0135] 38. The method according to any one of items 28 to 37, wherein the melt volume flow rate (as determined according to ISO 1133) increases by up to 20%, preferably up to 10%, and particularly preferably remains substantially the same after treatment, compared to the time point before the start of treatment.

[0136] 39. According to one of the methods in items 28 to 38,

[0137] The powder contains polyetherketone.

[0138] The polyetherketone ketone has the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at most 80%, preferably at most 70%, more preferably at most 65% and / or at least 20%, preferably at least 40%, more preferably at least 55%.

[0139] Where d 90 The value (determined according to ISO 13322-2) is at most 150 μm, preferably at most 100 μm, and / or

[0140] The bulk density after mechanical processing is at least 0.33 g / cm³. 3 Preferably at least 0.35 g / cm³ 3 More preferably at least 0.37 g / cm³ 3 Especially at least 0.39 g / cm³ 3 The value of .

[0141] 40. According to the method in Project 38,

[0142] The polyetherketone ketone has the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at most 80%, preferably at most 70%, more preferably at most 65% and / or at least 20%, preferably at least 40%, more preferably at least 55%.

[0143] 41. According to one of the methods in items 38 to 40,

[0144] The powder contains at least 15% by weight, preferably at least 20% by weight, of carbon fiber as filler and / or

[0145] The bulk density of the powder after mechanical processing is at least 0.50 g / cm³. 3 Preferably at least 0.52 g / cm³ 3 More preferably at least 0.54 g / cm 3 Even more preferably, at least 0.56 g / cm³ 3 The optimal value is at least 0.59 g / cm³. 3 The value of .

[0146] 42. According to one of the methods in items 38 to 41,

[0147] The BET surface area of ​​the powder after mechanical processing is at most 10 m². 2 / g, preferably up to 5m 2 / g, more preferably up to 2m 2 / g, or even more preferably up to 1.5m 2 / g, especially at most 1m 2 / g.

[0148] 43. According to one of the methods in items 28 to 38,

[0149] The powder contains polyetheretherketone (PEEK) or polyetheretherketone-polyether diphenyl etherketone (PEEK-PEDEK).

[0150] Among the powder's d 90 The maximum value (determined according to ISO 13322-2) is 150 μm, preferably 120 μm, more preferably 90 μm, and / or

[0151] The bulk density is at least 0.32 g / cm³. 3 Preferably at least 0.36 g / cm³ 3 Especially at least 0.40 g / cm 3 The value of .

[0152] 44. According to the method in Project 43,

[0153] The surface area of ​​BET is at most 40m² 2 / g, preferably up to 30m 2 / g, more preferably up to 20m 2 / g, and especially at most 2m 2 / g.

[0154] 45. The method according to any one of items 28 to 38, wherein the powder comprises polyphenylene sulfide,

[0155] Among the powder's d 90 The value is at most 150 μm (determined according to ISO 13322-2) and / or

[0156] The bulk density is at least 0.48 g / cm³. 3 Preferably at least 0.50 g / cm 3 Especially at least 0.52 g / cm³ 3 The value of .

[0157] 46. ​​According to the method in Project 45,

[0158] The surface area of ​​BET is at most 10m² 2 / g, preferably up to 7m 2 / g, more preferably up to 4m 2 / g, and especially at most 1m 2 / g.

[0159] 47. According to one of the methods in items 28 to 38,

[0160] The powder contains a polymer blend of polyphenylene sulfide and polyetherimide.

[0161] The molar ratio of polyphenylene sulfide to polyetherimide is at least 20:80, preferably at least 30:70, more preferably at least 40:60, particularly preferably at least 45:55 and / or at most 80:20, preferably at most 70:30, more preferably at most 60:40, particularly preferably at most 55:45, and

[0162] Among the powder's d 90 The value is at most 150 μm (determined according to ISO 13322-2) and / or

[0163] The bulk density is at least 0.32 g / cm³. 3 Preferably at least 0.36 g / cm³ 3 Especially at least 0.41 g / cm 3 The value of .

[0164] 48. According to one of the methods in items 28 to 38,

[0165] The powder contains polyamide 12.

[0166] Among the powder's d 90 The value is at most 150 μm, preferably at most 100 μm, more preferably at most 90 μm and especially at most 80 μm (determined according to ISO 13322-2) and / or

[0167] The bulk density is at least 0.35 g / cm³. 3 Preferably at least 0.37 g / cm³ 3 More preferably at least 0.40 g / cm 3 , and even more preferably at least 0.43 g / cm 3 And particularly preferred at least 0.44 g / cm³ 3 The value, and / or

[0168] The bulk density is at most 0.5 g / cm³. 3 The optimal concentration is at most 0.47 g / cm³. 3 More preferably up to 0.45 g / cm³ 3 The value of .

[0169] 49. According to the method in Project 48,

[0170] The surface area of ​​BET is at most 10m² 2 / g, preferably up to 7m 2 / g, more preferably up to 6m 2 / g, especially up to 4m 2 / g.

[0171] 50. According to one of the methods in items 28 to 38,

[0172] The powder contains polyamide 11.

[0173] Among the powder's d 90 The value is up to 150 μm, preferably up to 100 μm (determined according to ISO 13322-2) and / or

[0174] The bulk density is at least 0.35 g / cm³. 3 Preferably at least 0.37 g / cm³ 3 More preferably at least 0.40 g / cm 3 And particularly preferred at least 0.43 g / cm³ 3 The value, and / or

[0175] The bulk density is at most 0.6 g / cm³. 3 Preferred concentration: up to 0.53 g / cm³ 3 More preferably, up to 0.465 g / cm³ 3 The value of .

[0176] 51. According to the method in Project 50,

[0177] The surface area of ​​BET is at most 10m² 2 / g, preferably up to 7m 2 / g, more preferably up to 4m 2 / g, especially at most 1m 2 / g.

[0178] 52. The method according to any one of items 28 to 38, wherein the powder comprises polypropylene,

[0179] Among the powder's d 90 The value is up to 150 μm, preferably up to 100 μm (determined according to ISO 13322-2) and / or

[0180] The bulk density is at least 0.36 g / cm³. 3 Preferably at least 0.38 g / cm³ 3 A minimum of 0.40 g / cm³ is particularly preferred. 3 The value of .

[0181] 53. According to the method in Project 52,

[0182] The surface area of ​​BET is at most 10m² 2 / g, preferably up to 7m 2 / g, more preferably up to 4m 2 / g, especially at most 1m 2 / g.

[0183] The methods defined in one or more of items 30 to 52 may be advantageously combined with any methods defined in items 1 to 27, which are expressly included in this disclosure.

[0184] 54. A powder comprising at least one polymer for use in an additive manufacturing method for a three-dimensional object.

[0185] The powder is mechanically processed in the mixer using at least one rotating mixing blade.

[0186] Compared to the time before processing began, the time after processing...

[0187] —The bulk density of the powder is increased by at least 10%, and

[0188] —The BET surface area of ​​the powder is reduced by at least 10%.

[0189] —Optionally, fluidization capacity is also improved by at least 10%.

[0190] 55. Based on the powder in item 54,

[0191] The bulk density of the powder is increased by at least 15%, preferably at least 20%, more preferably at least 25%, and even more preferably at least 30%, and / or

[0192] The BET surface area of ​​the powder is reduced by at least 20%, preferably at least 30%, more preferably at least 40%, and even more preferably at least 60%.

[0193] 56. The powder according to any one of items 54 to 55, wherein the fraction of ultrafine powder is reduced by at least 5%, preferably at least 10%, more preferably at least 20%, or even more preferably at least 20%, after processing compared to the time point before the start of processing.

[0194] 57. A powder according to any one of items 54 to 56, wherein the powder comprises polyetherketoneketone.

[0195] The polyetherketone ketone has the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at most 80%, preferably at most 70%, more preferably at most 65% and / or at least 20%, preferably at least 40%, more preferably at least 55%, and

[0196] Where d 90 The value is at most 150 μm, preferably at most 100 μm (determined according to ISO 13322-2) and / or

[0197] The bulk density has a minimum of 0.33 g / cm³. 3 Preferably at least 0.35 g / cm³ 3 More preferably at least 0.37 g / cm³ 3Especially at least 0.39 g / cm³ 3 The value of .

[0198] 58. Based on the powder in item 57,

[0199] It has the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at most 70%, preferably at most 65%, more preferably at most 62% and / or at least 50%, preferably at least 55%, more preferably at least 58%.

[0200] 59. The powder according to one of items 57 or 58,

[0201] The powder contains at least 30% by weight, preferably at least 35% by weight, of carbon fiber as filler and / or

[0202] The bulk density has a minimum of 0.50 g / cm³. 3 Preferably at least 0.52 g / cm³ 3 More preferably at least 0.54 g / cm 3 It is still preferred to have at least 0.56 g / cm³. 3 And the optimal value is at least 0.59 g / cm³ 3 The value of .

[0203] 60. The powder according to one of items 57 to 59,

[0204] The BET surface area of ​​the powder is at most 10m². 2 / g, preferably up to 5m 2 / g, more preferably up to 2m 2 / g, or even more preferably up to 1.5m 2 / g, especially at most 1m 2 / g.

[0205] 61. Based on the powder of one of items 54 to 56,

[0206] The powder contains polyetheretherketone (PEEK) or polyetheretherketone-polyether diphenyl etherketone (PEEK-PEDEK), wherein the powder has:

[0207] powder d 90 The value (determined according to ISO 13322-2) is at most 150 μm, preferably at most 120 μm, more preferably at most 90 μm, and / or

[0208] The bulk density is at least 0.32 g / cm³. 3 Preferably at least 0.36 g / cm³ 3 Especially at least 0.40 g / cm 3 , and / or

[0209] The surface area of ​​BET is at most 40m² 2 / g, preferably up to 30m 2 / g, more preferably up to 20m 2 / g, with a maximum of 10mcg preferred 2 / g and especially at most 5m 2 / g.

[0210] 62. A powder according to any one of items 54 to 56, wherein the powder comprises polyphenylene sulfide,

[0211] Among the powder's d 90 The value is at most 150 μm (determined according to ISO 13322-2) and / or

[0212] The bulk density is at least 0.48 g / cm³. 3 Preferably at least 0.50 g / cm 3 Especially at least 0.52 g / cm³ 3 The value of .

[0213] 63. Based on the powder in item 62,

[0214] The surface area of ​​BET is at most 10m² 2 / g, preferably up to 7m 2 / g, more preferably up to 6m 2 / g, especially up to 4m 2 / g.

[0215] 64. The powder according to one of items 54 to 56,

[0216] The powder contains a polymer blend of polyphenylene sulfide and polyetherimide.

[0217] The molar ratio of polyphenylene sulfide to polyetherimide is at least 20:80, preferably at least 30:70, more preferably at least 40:60, particularly preferably at least 45:55 and / or at most 80:20, preferably at most 70:30, more preferably at most 60:40, particularly preferably at most 55:45, and

[0218] The molar ratio of polyphenylene sulfide to polyetherimide is preferably between 45:55 and 60:40, and is closer to 40:60 to 60:40.

[0219] Among the powder's d 90 The value is at most 150 μm (determined according to ISO 13322-2) and / or

[0220] The bulk density is at least 0.32 g / cm³. 3 Preferably at least 0.36 g / cm³ 3 Especially at least 0.41 g / cm3 The value of .

[0221] 65. A powder according to any one of items 54 to 56, wherein the powder comprises polyamide 12.

[0222] Among the powder's d 90 The value is at most 150 μm, preferably at most 100 μm, particularly preferably at most 90 μm and especially at most 80 μm (determined according to ISO 13322-2) and / or

[0223] The bulk density is at least 0.35 g / cm³. 3 Preferably at least 0.37 g / cm³ 3 More preferably at least 0.40 g / cm 3 It is still more preferable to have at least 0.43 g / cm³. 3 And particularly preferred at least 0.44 g / cm³ 3 The value of .

[0224] 66. Based on the powder in item 65,

[0225] The surface area of ​​BET is at most 10m² 2 / g, preferably up to 7m 2 / g, more preferably up to 4m 2 / g, especially at most 1m 2 / g.

[0226] 67. A powder according to any one of items 54 to 56, wherein the powder comprises polyamide 11.

[0227] Among the powder's d 90 The value is up to 150 μm, preferably up to 100 μm (determined according to ISO 13322-2) and / or

[0228] The bulk density is at least 0.35 g / cm³. 3 Preferably at least 0.37 g / cm³ 3 More preferably at least 0.40 g / cm 3 And particularly preferred at least 0.43 g / cm³ 3 The value of .

[0229] 68. Based on the powder in item 67,

[0230] The surface area of ​​BET is at most 10m² 2 / g, preferably up to 7m 2 / g, more preferably up to 4m 2 / g, especially at most 1m 2 / g.

[0231] 69. A powder according to any one of items 54 to 56, wherein the powder comprises polypropylene.

[0232] Among the powder's d 90 The value is up to 150 μm, preferably up to 100 μm (determined according to ISO 13322-2) and / or

[0233] The bulk density is at least 0.36 g / cm³. 3 Preferably at least 0.38 g / cm³ 3 A minimum of 0.40 g / cm³ is particularly preferred. 3 The value of .

[0234] 70. According to item 67, the powder in which the BET surface area is at most 10 m² 2 / g, preferably up to 7m 2 / g, more preferably up to 4m 2 / g, especially at most 1m 2 / g.

[0235] 71. A powder comprising at least one polymer for use in an additive manufacturing method of a three-dimensional object.

[0236] The powder contains polyetherketone.

[0237] The polyetherketone ketone has the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at most 80%, preferably at most 70%, more preferably at most 65% and / or at least 20%, preferably at least 40%, more preferably at least 55%.

[0238] Where d 90 The value is at most 150 μm (determined according to ISO 13322-2) and the bulk density therein has a minimum of 0.33 g / cm³. 3 Preferably at least 0.35 g / cm³ 3 More preferably at least 0.37 g / cm³ 3 Especially at least 0.39 g / cm³ 3 The value of .

[0239] 72. Based on the powder in item 71,

[0240] It has the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at most 70%, preferably at most 65%, more preferably at most 62% and / or at least 50%, preferably at least 55%, more preferably at least 58%.

[0241] 73. The powder specified in one of items 71 to 72,

[0242] The powder contains at least 30% by weight, preferably at least 35% by weight, of carbon fiber as filler and / or

[0243] The bulk density of the powder is greater than 0.50 g / cm³. 3 Preferably at least 0.55 g / cm³ 3 A minimum of 0.60 g / cm³ is preferred. 3 The value of .

[0244] 74. The powder according to one of items 71 to 73,

[0245] The BET surface area of ​​the powder is at most 10m². 2 / g, preferably up to 5m 2 / g, more preferably up to 2m 2 / g, or even more preferably up to 1.5m 2 / g, especially at most 1m 2 / g.

[0246] 75. A powder comprising at least one polymer for use in an additive manufacturing method for a three-dimensional object.

[0247] The powder contains polyetheretherketone (PEEK) or polyetheretherketone-polyether diphenyl etherketone (PEEK-PEDEK), wherein the powder has:

[0248] powder d 90 The value (determined according to ISO 13322-2) is at most 150 μm, preferably at most 120 μm, more preferably at most 90 μm, and / or

[0249] The bulk density is at least 0.32 g / cm³. 3 Preferably at least 0.36 g / cm³ 3 Especially at least 0.40 g / cm 3 .

[0250] 76. According to item 75, the powder in which the BET surface area is at most 40 m² 2 / g, preferably up to 30m 2 / g, more preferably up to 20m 2 / g, or even more preferably up to 10m 2 / g and especially at most 5m 2 / g.

[0251] 77. A powder comprising at least one polymer for use in an additive manufacturing method for a three-dimensional object.

[0252] The powder contains polyphenylene sulfide.

[0253] Among the powder's d 90The value is at most 150 μm (determined according to ISO 13322-2) and / or

[0254] The bulk density is at least 0.48 g / cm³. 3 Preferably at least 0.50 g / cm 3 Especially at least 0.52 g / cm³ 3 The value of .

[0255] 78. Based on the powder in item 77,

[0256] The surface area of ​​BET is at most 10m² 2 / g, preferably up to 7m 2 / g, more preferably up to 6m 2 / g, especially up to 4m 2 / g.

[0257] 79. A powder comprising at least one polymer for use in an additive manufacturing method for a three-dimensional object.

[0258] The powder contains a polymer blend of polyphenylene sulfide and polyetherimide.

[0259] The molar ratio of polyphenylene sulfide to polyetherimide is at least 40:60, preferably at least 45:55 and / or at most 60:40, preferably at most 55:45, and

[0260] Among the powder's d 90 The value is at most 150 μm (determined according to ISO 13322-2) and / or

[0261] The bulk density is at least 0.32 g / cm³. 3 Preferably at least 0.36 g / cm³ 3 Especially at least 0.41 g / cm 3 The value of .

[0262] 80. A powder comprising at least one polymer for use in an additive manufacturing method of a three-dimensional object.

[0263] The powder contains polyamide 12.

[0264] Among the powder's d 90 The value is at most 150 μm, preferably at most 100 μm, particularly preferably at most 90 μm and especially at most 80 μm (determined according to ISO 13322-2) and / or

[0265] The bulk density is at least 0.35 g / cm³. 3 Preferably at least 0.37 g / cm³ 3 More preferably at least 0.40 g / cm 3It is still more preferable to have at least 0.43 g / cm³. 3 And particularly preferred at least 0.44 g / cm³ 3 The value of .

[0266] 81. Based on the powder of item 80,

[0267] The surface area of ​​BET is at most 10m² 2 / g, preferably up to 7m 2 / g, more preferably up to 4m 2 / g, especially at most 1m 2 / g.

[0268] 82. A powder comprising at least one polymer for use in an additive manufacturing method for a three-dimensional object.

[0269] The powder contains polyamide 11.

[0270] Among the powder's d 90 The value is at most 150 μm, preferably at most 100 μm (determined according to ISO 13322-2) and / or

[0271] The bulk density has a minimum of 0.35 g / cm³. 3 Preferably at least 0.37 g / cm³ 3 More preferably at least 0.40 g / cm 3 And particularly preferred at least 0.43 g / cm³ 3 The value of .

[0272] 83. Based on the powder in item 82,

[0273] The surface area of ​​BET is at most 10m² 2 / g, preferably up to 7m 2 / g, more preferably up to 6m 2 / g, especially up to 4m 2 / g.

[0274] 84. A powder comprising at least one polymer for use in an additive manufacturing method for a three-dimensional object.

[0275] The powder contains polypropylene.

[0276] Among the powder's d 90 The value is up to 150 μm, preferably up to 100 μm (determined according to ISO 13322-2) and / or

[0277] The bulk density is at least 0.36 g / cm³. 3 Preferably at least 0.38 g / cm³ 3 A minimum of 0.40 g / cm³ is particularly preferred. 3The value of .

[0278] 85. Based on the powder in item 84,

[0279] The surface area of ​​BET is at most 10m² 2 / g, preferably up to 7m 2 / g, more preferably up to 4m 2 / g, especially at most 1m 2 / g.

[0280] The powder defined in one or more of items 53 to 84 may be advantageously obtained by any of the methods defined in items 1 to 52, which are expressly included in this disclosure.

[0281] 86. The method or powder specified in any of the foregoing items,

[0282] The powder comprises at least one polymer selected from the group consisting of at least two polymers selected from the group consisting of:

[0283] Polyetherimide, polycarbonate, polyaryl sulfide, polyphenylsulfone, polysulfone, polyphenylene ether, polyethersulfone, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene-acrylate copolymer (ASA), polyvinyl chloride, polyacrylate, polyester, polyamide, polyaryl ether ketone, polyether, polyurethane, polyimide, polyamide-imide, polysiloxane, polyolefin, and copolymers having at least two different repeating units of the above polymers.

[0284] This group preferably consists of polyaryletherketones, polyphenylene sulfides, polycarbonates, polyetherimides, polypropylene, polyethylene, and polyamides, as well as their copolymers and polymer blends.

[0285] More preferably, the powder contains at least one polyaryletherketone, and even more preferably, the powder contains polyetherketoneketone and / or polyetheretherketone-polyetherdiphenyletherketone (PEEK-PEDEK).

[0286] 87. According to the method or powder of item 86, respectively, wherein the powder comprises polyetherketoneketone and

[0287] The polyetherketone ketone has the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at most 80%, preferably at most 70%, more preferably at most 65% and / or at least 20%, preferably at least 40%, more preferably at least 55%.

[0288] 88. According to the method or powder of one of items 86 or 87 respectively, wherein the polymer is polyaryletherketone,

[0289] The polyaryletherketone has a melting point T of up to 330°C, preferably up to 320°C, and particularly up to 310°C. m (as determined according to DIN EN ISO 11357), and / or

[0290] Among them, polyaryletherketone has a glass transition temperature T. g (Measured according to DIN EN ISO 11357) at least 120°C, preferably at least 140°C, and especially at least 160°C.

[0291] 89. According to the method or powder of item 86 respectively, wherein the polymer is polyetherimide and

[0292] Preferably, the polyetherimide comprises a repeating unit according to the following formula I

[0293]

[0294] And / or based on the following repeating units

[0295] Formula II

[0296]

[0297] And / or based on the following repeating units

[0298] Formula III

[0299]

[0300] 90. According to the method or powder of item 86 respectively,

[0301] The polymer is polycarbonate and

[0302] Preferably, the polycarbonate comprises repeating units according to the following

[0303] Formula IV

[0304]

[0305] 91. According to the method or powder of item 86 respectively,

[0306] The polymer is a polyarylene sulfide, preferably a polyphenylene sulfide, which comprises repeating units according to the following

[0307] Formula V

[0308]

[0309] 92. According to the method or powder of item 86 respectively, wherein the polymer is a polymer blend,

[0310] The polymer blends include polyaryletherketone-polyetherimide, polyaryletherketone-polyetherimide-polycarbonate, polyphenylene sulfide-polyetherimide and / or polyetherimide-polycarbonate.

[0311] 93. According to the method or powder of item 92 respectively,

[0312] The polyaryletherketone of the polymer blend is preferably a polyetherketone ketone having a terephthalic acid / isophthalic acid isomer ratio between 65 / 35 and 55 / 45, and / or

[0313] The polyetherimide in the polymer blend comprises a repeating unit of Formula I as defined in item 89 above, and / or

[0314] Polycarbonate comprises repeating units according to the following

[0315] Formula IV

[0316]

[0317] and / or

[0318] Polyphenylene sulfide comprises repeating units according to the following

[0319] Formula V

[0320]

[0321] 94. A method or powder according to any one of the foregoing items, wherein the powder comprises polyetherketone ketone having the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at most 80%, preferably at most 70%, more preferably at most 65%, and / or

[0322] The powder contains polyetherketone ketone, which has the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at least 20%, preferably at least 40%, and more preferably at least 55%.

[0323] 95. The method or powder according to any one of the foregoing items, wherein the powder to be treated contains at least one additive, preferably a filler.

[0324] Fiber fillers, particularly carbon fiber fillers, are especially preferred, and are preferably substantially completely embedded in the polymer matrix.

[0325] The additives are preferably one or more of the following materials: heat stabilizers, oxidation stabilizers, UV stabilizers, fillers, dyes, plasticizers, reinforcing fibers, dyes, IR absorbers, SiO2 particles, carbon black particles, carbon fibers optionally containing carbon nanotubes, glass fibers, mineral fibers, especially wollastonite, aramid fibers, especially Kevlar fibers, glass beads, mineral fillers, inorganic and / or organic pigments and / or flame retardants, especially phosphate-containing flame retardants, such as ammonium polyphosphate and / or brominated flame retardants and / or other halogenated flame retardants and / or inorganic flame retardants, such as magnesium hydroxide or aluminum hydroxide, flow aids, especially polysiloxanes, and fluidizing aids, especially pyrolytic silica. Powdered materials may also contain several different additives; for example, polycarbonate may contain UV stabilizers and flame retardants.

[0326] Preferably, the starting powder subjected to the actual mechanical processing according to the present invention does not contain fluidizing agents because the presence of fluidizing agents during the actual thermomechanical processing can lead to a decrease in bulk density.

[0327] 96. Based on the method or powder of any one of the aforementioned items,

[0328] The powder is prepared by a selection of pulverizing techniques, including grinding, particularly low-temperature grinding of coarse powder or granules, solvent precipitation, spray drying, melt spraying, melt dispersion, and melt spinning, including fiber cutting.

[0329] The powder defined in one or more of items 78 to 95 may be advantageously obtained by any of the methods defined in items 1 to 52, which are expressly included in this disclosure.

[0330] 97. A method for additive manufacturing of a three-dimensional object, comprising the following steps:

[0331] To manufacture three-dimensional objects by means of powder according to any of the foregoing items; and by means of electromagnetic radiation, particularly by selective laser sintering, selectively solidifying the powder layer by layer at positions corresponding to the cross-section of the object in the respective layers.

[0332] The present invention enables the provision of powders in a manner not conventionally considered or anticipated, powders designated for additive manufacturing of three-dimensional objects, and the use of such powders preferably achieves improved mechanical properties of the manufactured three-dimensional objects.

[0333] Furthermore, it is surprising that the supplied powder can be processed with a low update factor in the fabrication of 3D objects. This means that when reusing powder already used in the additive manufacturing process (the so-called "old powder"), only a small amount of powder not yet used in the additive manufacturing process (the so-called "new powder") needs to be added. Additionally, it is preferable that the supplied powder can be processed in a process with an expanded process window. This means an increased distance between the upper and lower build temperatures during the addition process.

[0334] In the process of the method according to the invention, the mechanical energy of the rotating mixing blades of the mixer is converted into heat energy, thereby heating the powder, which is the mixing material in the mixer. Simultaneously, the powder is subjected to mechanical stress, particularly shear, from the mixing blades. Through a combination of heat treatment and mechanical treatment (also known simply as "thermomechanical treatment"), improvements in powder properties can be achieved, such as increased bulk density, reduced BET surface area, improved applicability of powder layer forms, increased sphericity of powder particles, and reduced roughness.

[0335] Preferably, thermomechanical treatment can also reduce the fraction of ultrafine particles (<10 μm), i.e., the ultrafine powder content. Ultrafine particles are often disruptive during laser sintering because they impair process stability. Electrostatic charging, in particular, can lead to deterioration of fluidization capacity and thus powder application. The higher the proportion of ultrafine particles in the powder, the greater the tendency for electrostatic charging. Ultrafine powder can be compressed into larger powder particles by mechanical energy at a suitable temperature, which, in addition to reducing the ultrafine powder content, also leads to a reduction in the BET surface area.

[0336] It has been found that powdered materials with high packing density can be used to prepare three-dimensional objects with low porosity, and therefore have better mechanical properties than three-dimensional objects made from powders with low packing density.

[0337] Because additive manufacturing is a process that does not compress powder by pressure, unlike injection molding and similar technologies, packing density is crucial in additive manufacturing. In other words, powder particles must flow well into each other without the application of pressure in order to maintain low porosity.

[0338] If powders have an unfavorable powder morphology after polymerization and pulverization, they typically also have poor fluidization capabilities and can be inadequately metered or applied. An unfavorable powder morphology is particularly characterized by powder particles that are more fibrous than spherical or potato-shaped.

[0339] According to the invention, the powder may also have improved fluidization capabilities. This improved layer application and powder metering result in less frequent or even completely avoided process instability.

[0340] According to the present invention, the powder may also have a particularly low BET surface area, which also leads to improved processability of the powder and further improved mechanical properties of the three-dimensional objects thus prepared.

[0341] Furthermore, X-ray diffraction revealed that the treatment according to the method of the present invention resulted in a change in the crystallinity of the powder particles in the surface region compared to the untreated powder.

[0342] This demonstrates that the surface of powder particles can be modified by the method according to the invention. Within the scope of the invention, additional processing steps can be added to the mechanical processing according to the invention, wherein the surface can be further modified. In summary, surface modification can be combined in this manner.

[0343] Microscopic and electron microscopic methods have confirmed that the method according to the invention results in the smoothing of powder particles. Powders with smoother powder particles generally have a higher packing density compared to powders with relatively coarse powder particles.

[0344] Within the scope of the method according to the invention, the rapid heating of the powder, simultaneously creating shear stress on the powder particles, avoids the need to heat the powder to such high temperatures that damage to the powder would occur. Such high temperatures can have adverse effects, for example, altering the melt viscosity and other properties of the powder due to increased molar mass, degradation, or cross-linking. This, in turn, can result in no negative changes to the mechanical properties and / or renewal factor of the powder and / or the process window of the powder during processing in additive manufacturing.

[0345] By rapidly heating powder particles according to the present invention, significantly less heating can be achieved in the core region of the powder particles compared to their outer regions. Compared to powder particles that are similarly and intensely heated in both the core and outer regions, powder particles with lower core heating intensity exhibit greater dimensional stability against shear stresses caused by mixing. Slow heating of the powder results in the core of the powder particles being heated more than in cases of rapid heating. Rapid heating, in particular, smooths the outer regions of the powder particles, especially without causing deformation.

[0346] Furthermore, the rapid heating and treatment at relatively low temperatures according to the invention prevent excessive increases in the melt viscosity of the polymer. This advantageous effect is particularly strong in the cases of polyaryletherketones and polyphenylene sulfides. In the case of polymers prepared by polycondensation reactions under dehydration, such as polyamides and polyesters, depending on the end-group ratio and stability, treatment at high temperatures can lead to increases or decreases in melt viscosity due to post-condensation, and prolonged degradation reactions can occur due to insufficient stability. In the case of polyolefins such as polypropylene or polyethylene, a decrease in free radical molar mass can occur due to excessively high temperatures and insufficient stability.

[0347] Changes in melt viscosity can be determined based on melt flow index measurements: the lower the melt volumetric flow rate (often referred to as "MVR"), the higher the melt viscosity.

[0348] The problems avoided by rapid heating occur particularly in the case of specialized heat treatment (“tempering”) of powders. During tempering, the powder is heated by a heater rather than mechanically processed by a mixer. In fact, the temperature applied for tempering is usually higher than that in the case of the present invention, i.e., thermomechanical processing. Furthermore, the temperature distribution in the powder is uneven during tempering, resulting in particularly strong overheated areas. In addition, the powder processing during tempering is usually carried out for a relatively long period of time. According to the present invention, the problems associated with specialized heat treatment of powders can be reduced or even completely avoided.

[0349] Therefore, the improvement in bulk density and BET surface area achieved by the present invention is not as significant as that achieved by specialized heat treatment of polymer powders.

[0350] In the case of some powders, particularly those containing PAEK, it has been shown that pure heat treatment of the powder following thermomechanical treatment according to the invention is advantageous. Pure heat treatment can be carried out, for example, in an oven.

[0351] According to the present invention, after a very short processing time of less than, for example, 30 minutes (which is significantly reduced compared to the prior art), the properties of powders containing polyaryletherketone (PAEK), particularly powders containing polyetherketoneketone (PEKK), can be significantly improved. This is a significant improvement in the economic efficiency of the method.

[0352] The inventors have recognized that, in combination with the above-mentioned advantages possible according to the invention, it is important to apply high shear energy to the powder in the shortest possible time without overheating the powder.

[0353] Depending on the number and geometry of the mixing blades, the geometry of the container in which the powder resides during mixing, the degree of filling of the mixer, the cooling of the mixer, particularly the mixer jacket, and the initial bulk density, the rotational speed of the mixing blades, and the processing time are selected. The rotational speed of the mixing blades need not be constant, but can be varied during the process according to the method of the present invention.

[0354] According to the preferred embodiment, the rotational speed of the mixing blades is selected in such a way that the powder reaches the desired processing temperature in the shortest possible time and then does not exceed that temperature (exceeding the desired temperature is "overheating"), that is, the temperature is maintained for the remaining processing time such that it does not exceed the upper limit and does not drop below the lower limit.

[0355] In particular, for powders containing PAEK, it was surprisingly found that a thermomechanical treatment duration of less than 30 minutes (for heating and holding the temperature) was sufficient to achieve improved or even optimized results.

[0356] The mixer preferably has at least two mixing blades, and more particularly preferably at least three mixing blades, which are preferably offset from each other by 90°. The mixing blade arrangement is particularly preferably three mixing blades, of which at least two are curved and one is straight. The number and geometry of the mixing blades have a decisive influence on the applied shear energy and therefore on the processing duration.

[0357] Typically, the rotational speed is 20-40 m / s to heat the powder quickly enough without overheating it.

[0358] The method according to the invention has proven particularly advantageous when the polymer is harder than that of a typical elastomer.

[0359] Preferably, the powder contains at least one of the above-described polymers or polymer blends.

[0360] Further features and advantages of the invention can be found in the description of the embodiments and examples with reference to the accompanying drawings.

[0361] Figure 1 A schematic diagram and vertical cross-sectional view of an apparatus for additive manufacturing of three-dimensional objects are shown.

[0362] Figure 2 This illustrates a hybrid blade arrangement that can be used according to the present invention.

[0363] Figure 3 The curve showing the relationship between packing density and total processing time for an example of the present invention is displayed.

[0364] Figure 4 This shows a curve of bulk density versus maximum temperature in the mixer during processing, for another embodiment of the invention.

[0365] Figure 5 This shows the relationship between the maximum temperature and powder mass for this instance, with the actual dependent variable plotted on the horizontal axis.

[0366] Figure 6 The figure shows the curve of packing density versus total processing time for another embodiment of the invention.

[0367] Figure 7 This shows the curve of packing density versus residence time for this example.

[0368] Figure 8 The temperature-current consumption graph shows the change in current consumption in the mixer over time compared to the temperature increase in Experiment V23 of Example 5.

[0369] Figure 9 The temperature-current consumption graph shows the change in current consumption in the mixer over time compared to the temperature increase in Experiment V3 of Example 10.

[0370] Figure 10 The temperature-current consumption graph shows the change in current consumption in the mixer over time during the heating phase, compared to the temperature increase in Experiment V4 of Example 11.

[0371] Figure 11 The temperature-current consumption graph shows the change in current consumption in the mixer over time compared to the temperature increase in Experiment V2 of Example 12.

[0372] Figure 12 The temperature-current consumption graph shows the change in current consumption in the mixer over time compared to the temperature increase in Experiment V9 of Example 13.

[0373] Figure 1 The apparatus shown is a laser sintering or laser melting apparatus 1 for manufacturing an object 2 from a powdered material 15. The powdered material 15 is also referred to in this context as a "construction material." For information on the selection of the powdered material, please refer to the description above.

[0374] The apparatus 1 includes a process chamber 3 with cavity walls 4. Within the process chamber 3, a container 5 with an opening at the top is provided with container walls 6. A working plane 7 is defined by the upper opening of the container 5, and the area of ​​the working plane 7 located within the opening that can be used to construct the object 2 is referred to as a construction area 8. Within the container 5, there is a support 10 movable in the vertical direction V, to which a substrate 11 is connected. This support closes the container 5 at the bottom and thus forms the container bottom. The substrate 11 may be a plate formed separately from and connected to the support 10, or it may be integrally formed with the support 10. Depending on the powder used and the process, the substrate 11 may also have a construction platform 12 connected as a construction base on which the object 2 is constructed. However, the object 2 may also be constructed on the substrate 11 itself, whereby the substrate 11 acts as a construction base. Figure 1 The object to be constructed is shown in an intermediate state. It consists of multiple cured layers and is surrounded by uncured powdery material 13.

[0375] Furthermore, the apparatus 1 includes a storage container 14 for a powdered material 15 that can be solidified by electromagnetic radiation and a recoating device 16 that can move horizontally in the direction H to apply a layer of the powdered material 15 within the build area 8. Preferably, a radiation heater 17 is arranged in the process chamber 3 for heating the applied powdered material 15. For example, an infrared radiator 17 can be provided as the radiation heater 17.

[0376] In addition, the device 1 includes a radiation device 20 having a laser 21 that generates a laser beam 22, which is deflected by a deflection device 23 and focused by a focusing device 24 onto the working plane 7 via a coupling window 25 disposed at the top of the process cavity 3 in the cavity wall 4.

[0377] Furthermore, the device 1 includes a control device 29 by means of which the various components of the device 1 are controlled in a coordinated manner to perform a method for manufacturing a three-dimensional object 2. The control device 29 may include a CPU, the operation of which is controlled by a computer program (software). The computer program may be stored separately from the device 1 on a storage medium, from which the computer program can be loaded into the device 1, and particularly into the control device 29.

[0378] For example, laser sintering apparatuses with type names P110, P396, P500, P770, P800 and P810 provided by the applicant have proven to be suitable for carrying out the present invention.

[0379] During operation, in order to apply a layer of powdered material 15, the support 10 is lowered, preferably to a height corresponding to the desired thickness of the powdered material 15 layer. The recoater 16 first moves to the storage container 14 and removes a sufficient amount of powdered material 15 to apply one layer. The recoater 16 then moves over the build area 8 and applies a thin layer of powdered material 15 to the build bases 10, 11, 12, or a previously existing powder layer. Application is performed at least over the entire cross-section of the object to be prepared, preferably over the entire build area 8. Preferably, the powdered material 15 is heated to the processing temperature by a radiation heater 17. The cross-section of the object 2 to be prepared is then scanned by a laser beam 22, causing the applied layer to solidify in that area. These steps are repeated until the object 2 is complete and can be removed from the container 5.

[0380] This invention is preferably applied to, but not limited to, laser sintering or laser melting. It can be applied to various methods, as long as these involve preparing three-dimensional objects by means of applying and selectively solidifying powdered materials layer by layer through exposure to electromagnetic radiation.

[0381] The radiation device 20 may, for example, comprise one or more gas lasers or solid-state lasers or any other type of laser, such as laser diodes, particularly a line exposure device using VCSELs (vertical-cavity surface-emitting lasers) or VECSELs (vertical-external-cavity surface-emitting lasers). Generally, any radiation source suitable for selectively applying electromagnetic radiation to a layer of powdered material 15 can be used as the radiation device. For example, instead of a laser, another light source suitable for curing powdered material 15 or any other electromagnetic radiation source can be used. Instead of deflecting the beam, exposure with a movable line radiator can also be used. The invention can also be applied to selective mask sintering, where a light source radiating over a region and a mask is used, or to high-speed sintering (HSS), where material is selectively applied to powdered material 15, which increases radiation absorption at locations corresponding to the cross-section of the three-dimensional object 2 (absorbent sintering) or reduces radiation absorption at other locations in the build region 8 (inhibitory sintering), and then non-selectively exposed over a large area or using a movable line radiator.

[0382] According to the invention, it is preferable to preheat the powder material 15 before selectively sintering, melting and solidifying it by exposing it to electromagnetic radiation. During the preheating process, the powder material 15 is heated to an elevated processing temperature so that less energy introduced by the electromagnetic radiation is used for selective solidification.

[0383] In the context of this invention, commercially available mixers may be used.

[0384] For example, a Henschel mixer model FML with a machine size of 40, from the supplier Zeppelin Systems GmbH in Germany, can be used. This mixer will be referred to as "Henschel FML" below. During operation, the mixing chamber containing the materials to be mixed has a usable volume of 13 to 36 liters.

[0385] The fill factor of the mixer is the quotient of the volume of powder filled into the mixer and the volume of the mixing chamber of the mixer. The volume of powder is determined before proceeding with the method according to the invention. Hereinafter, the fill factor is referred to as F.

[0386] Alternatively, a mixer such as the "Mixaco LAB-CM 6-12MB / SM" with a 6-liter container can be used.

[0387] However, other mixers may also be used, especially other commercially available mixers that allow for the processing of larger quantities of powder in kilograms within a single batch.

[0388] exist Figure 2The mixed blade arrangement 100 is schematically shown in the figure. Examples 1 to 8 can be implemented using such a mixed blade arrangement 100.

[0389] The mixing blade arrangement 100 has a shaft 107 along its length. A bottom scraper 105, three straight mixing blades 101, 102, and 103, and an upwardly curved mixing rod 106 are connected to this shaft in this order. The mixing blades are generally referred to as "mixer blades." The mixing blades 101, 102, and 103 are straight, i.e., neither curved upwards nor downwards. Therefore, the bottom scraper 105 and the mixing rod 106 are examples of non-straight mixing blades. The mixing blades 101, 102, and 103 may preferably be arranged at an angle around the shaft 107. In particular, the distances (referred to as y1, y2, y3, and y4) between the bottom scraper 105, the mixing blades 101, 102, and 103, and the mixing rod 106 are generally in the range of 10 to 40 mm, preferably in the range of 25 to 35 mm. The maximum lateral extension of the bottom scraper 105, mixing blades 101, 102, 103, and mixing rod 106 is specified as x. x corresponds to twice the radius r of the mixing blades. x is preferably in the range of 100 to 1000 mm, more preferably in the range of 200 to 900 mm. In the case of the mixer "Henschel FML" type, the machine size is 40, where the inner diameter of the mixing container is 386 mm and the height of the mixing container is 396 mm, x = 350 mm. In the case of the mixer model "Henschel FML", the machine size is 600, where the inner diameter of the mixing container is 1330 mm and the height of the mixing container is 1370 mm, x = 870 mm. In the case of the mixer "Mixaco LAB-CM 6-12CM / SM" type, where the container size (volume of the mixing container) is 6 liters, x = 222.8 mm.

[0390] For mixer model "Henschel FML" with a machine size of 40, a mixer with a bottom scraper 105, a mixing rod 106, and straight mixing blades 101 is preferred. For mixer model "Henschel FML" with a machine size of 600, a mixer with a bottom scraper 105, a mixing rod 106, and three straight mixing blades 101, 102, and 103 is preferred. Therefore, the preferred number of mixing blades 101, 102, and 103 depends on the size of the mixer used.

[0391] Preferably, the hybrid blades 101, 102, and 103 are arranged in a twisted manner relative to the shaft. For example, based on Figure 2 As shown in the diagram, the hybrid blade 102 can be arranged by rotating 90° relative to the other hybrid blades 101 and 103.

[0392] During operation, the mixing blade assembly 100 is located inside the mixing container. Figure 2 (not shown), the powder to be processed according to the method of the present invention ( Figure 2 (Not shown in the image) is also located inside the mixing container. The bottom scraper 105 is arranged closer to the bottom of the mixing container than the mixing blades 101, 102, 103 and the mixing rod 106.

[0393] During operation, shaft 107 rotates about its own axis by means of a motor. Rotation is indicated by arrow 108. The bottom scraper 105, mixing blades 101, 102, 103 and mixing rod 106 are preferably arranged rotationally symmetrically with respect to shaft 107 so that no imbalance occurs when the shaft rotates. Example

[0394] The following describes some embodiments of the present invention. These embodiments are intended to illustrate the invention and therefore do not limit its scope in any way. It will be apparent to those skilled in the art that the embodiments described below can be changed and modified within the context of the entire disclosure. Features of individual embodiments may be combined with each other when possible.

[0395] Example 1

[0396] In Example 1, polyphenylene sulfide powder was used. Polyphenylene sulfide (also known as poly(thio-p-phenylene) and often abbreviated as "PPS") is a high-temperature resistant thermoplastic having the following repeating units:

[0397]

[0398] The product used was a commercially available one, supplied by Toray Industries, Inc. of Japan under the trade name "Toray 50NNAB". The quantiles d measured prior to the method according to the invention are given in the first row, "Comparison," of Table 3. 10 d 50 and d 90 .

[0399] A "Henschel FML" model mixer was used as the mixer. The jacket of the uncooled mixer was also present.

[0400] Stage 1 refers to the heating stage, which continues until the mixed material (powder) in the mixer reaches its maximum temperature T. max The stage of time. T max Corresponding to processing temperature T B The mixer jacket only reaches a relatively low temperature T. ManThe mixer's rotational speed in stage 1 is called D1. The duration of stage 1 is called t1. Stage 2 is the residence stage, which is the stage in which the achieved temperature is maintained. The mixer's rotational speed in stage 2 is called D2. The duration of stage 2 is called t2.

[0401] In another embodiment, the symbol T is used in the same manner. Max T Man D1, D2, t1, t2.

[0402] The method according to the invention was performed three times using independent powder batches (1 to 3). The T values ​​for powder batches 1 to 3 are recorded in Table 2. Max T Man The values ​​of D1, D2, t1, t2 and t1+t2.

[0403] Table 3 presents the following values ​​obtained for 1 to 3: bulk density S, BET surface area, powder particle fraction with a particle size <10 μm by volume percentage (% <10 μm), and quantile of particle size distribution d. 10 d 50 and d 90 The fluidization capacity was measured using a 25mm nozzle. These are averages from three measurements each. Control values ​​for PPS powder not treated according to the present invention are also given in Table 3. If no value is recorded in a column or row, it means that no corresponding measurement was performed.

[0404] Table 2

[0405]

[0406] Table 3

[0407]

[0408] exist Figure 3 In the figure, the achieved bulk density is plotted relative to the total processing time t1+t2. Data points where t1+t2=0 represent PPS powder that was not processed according to the method of the invention. Figure 3 It can be clearly seen that, through the treatment according to the present invention, temperatures above the glass transition temperature T are achieved. g A significant increase in packing density (PPS T) was achieved at a temperature of [temperature value missing]. g ≈90 to 110°C, or 105°C for the PPS used in this paper; compare with Table 2 for the temperatures Tmax that occurred during the treatment. This effect was achieved with a total treatment time of 17 min. For example, at temperatures between 105°C and 180°C, depending on the preparation method.

[0409] In addition, the treatment significantly improves fluidization. Although the powder ground before the treatment according to the invention does not flow freely during this period, it exhibits good flowability after about 5 seconds (tested using a 25 mm nozzle), see Table 3.

[0410] Furthermore, through the processing according to the present invention, the BET surface area is increased from approximately 16 m². 2 / g decreased drastically to approximately 8m 2 / g, see Table 3.

[0411] Furthermore, by processing according to the present invention, the fine powder fraction is significantly reduced from about 0.4% to about 0.2%, see Table 3.

[0412] Example 2

[0413] In Example 2, a polymer blend of 50 wt% PPS and 50 wt% polyetherimide (PEI) was used. A total of 1.65 kg of the polymer blend powder was used in Example 2. The powder obtained by cryogenic milling using a needle mill was fibrous and had a density of approximately 0.27 g / cm³. 3 The packing density is very low. The quantiles d measured prior to the method according to the invention are given in the first row of Table 5. 10 d 50 and d 90 .

[0414] A "Mixaco LAB-CM 6-12CM / SM" type mixer with a container size of 6 liters is used as the mixer. The jacket of the uncooled mixer is not used.

[0415] T is provided in Table 4 Max T Man The values ​​of D1, D2, t1, t2 and t1+t2, wherein the number of powder batches in Example 2 is 4.

[0416] The following values ​​were obtained, given in Table 5: bulk density S and quantiles of particle size distribution d. 10 d 50 and d 90 These are the averages of three measurements each. Comparative values ​​for the PPS-PEI polymer blend powder, which was not processed according to the invention, are also given in Table 5. If no value is recorded in a column or row, it means that no corresponding measurement was performed.

[0417] Table 4

[0418]

[0419] Table 5

[0420]

[0421] By processing according to the present invention, T is higher than PPS. g Value (T) g At approximately 90 to 100°C, the bulk density can be significantly increased to 0.428 g / cm³. 3 This corresponds to a 57% increase.

[0422] Use T higher than PEI g Temperatures below the melting point of PPS (approximately 275°C) can optionally achieve or even more significantly increase bulk density.

[0423] Example 3

[0424] In Example 3, a copolymerization ratio of approximately 60:40 for terephthalic acid units to isophthalic acid units of polyetherketoneketone (PEKK) was used. This is a PAEK plastic.

[0425] Use a commercially available product, marketed under the trade name "Kepstan 6002PF" by Arkema SA in France. Grind this coarse powder and sieve it to the appropriate particle size.

[0426] A "Henschel FML" model mixer was used as the mixer. The mixer jacket was cooled by water cooling.

[0427] The method according to the invention was performed six times using independent powder batches (numbers 5 to 10). The mass of the powder batch is specified as m. The T values ​​for batch numbers 6 to 10 are provided in Table 6. max T Man The values ​​of m, F, D1, D2, t1, t2, and t1+t2. F is the fill level of the mixer. The symbols are used in the same manner in other embodiments.

[0428] Table 7 presents the following values ​​obtained: bulk density S, BET surface area, fraction of powder particles with a particle size <10 μm by volume (% <10 μm), and quantile of particle size distribution d. 10 d 50 and d 90 These are averages from three measurements each. Table 7 also provides control values ​​for 60:40 PEKK powder that was not treated according to the method of the invention. If no value is recorded in a column or row, it means that no corresponding measurement was performed.

[0429] Table 6

[0430]

[0431]

[0432] Table 7

[0433]

[0434] PEKK powders with a copolymerization ratio of terephthalic acid units to isophthalic acid units of approximately 70:30 to approximately 10:90, particularly approximately 60:40, exhibit the following unique properties: if the powders are obtained through polymerization and, possibly, pulverization, they are typically semi-crystalline. However, if the cooling rate is less than 5 °C / min, the polymer typically crystallizes only from the melt, considering the case where the polymer does not contain any filler (unfilled PEKK). In this respect, it behaves more like an amorphous polymer than a semi-crystalline polymer.

[0435] If the powder exhibits amorphous behavior due to rapid cooling, the HDT-A value is 139°C. The HDT-B value is close to T. g (Approximately 155°C). If the powder exhibits semi-crystalline behavior due to slower cooling, the HDT-A value is at T... g and T m between.

[0436] Heated to T g During this process, a significant and potentially maximum increase in packing density can be achieved. However, even at T... g Even at +20℃, a significant increase in bulk density can still be achieved. The 60:40 copolymer has a Tg of 155℃. g Its melting point is approximately 300°C.

[0437] Significant and potentially maximum increases in bulk density have been achieved with processing times significantly shorter than 30 minutes. Here, the processing time depends on the initial bulk density of the powder (also compared with Examples 4 and 5) and the mass m of the powder in the mixer.

[0438] The bulk density can be increased according to the processing temperature. The preferred processing temperature is between 110 and 155°C. Above T... g The bulk density decreased slightly again (also compared to Examples 4 and 5). Below 90°C, the bulk density had not yet reached its maximum.

[0439] exist Figure 4 In this context, the achieved packing density is relative to the maximum temperature T that occurs during the processing. max Drawing. T max Data points at 20°C (room temperature) represent 60:40 PEKK powder that has not been treated according to the method of the present invention. From Figure 4It can be clearly seen that the processing according to the invention achieves a very strong improvement in packing density at temperatures above approximately 90°C, and particularly at temperatures around 120°C, the optimized maximum packing density is achieved.

[0440] The maximum achievable temperature in a mixer used at the maximum possible rotational speed of 2600 rpm depends on the degree of packing in the mixer. For the polymer powder used in this embodiment, only enough shear energy is introduced into the mixer for a mass exceeding approximately 9 kg, allowing the temperature to rise to approximately 110°C or higher when the mixer jacket is cooled with water. Figure 5 The text displays the powder mass m and T. max The relationship between them is plotted on the horizontal axis, where the actual dependent variable T is shown. max .

[0441] For other types of mixers or mixers of other sizes, a powder mass other than 9 kg may be more suitable. This must be determined iteratively for each mixer and each type of powder. This determination can be based on... Figure 5 The series of measurement results shown in the image correspond to a series of measurements.

[0442] Example 4

[0443] In Example 4, PEKK, which was also used in Example 3, was used with a copolymerization ratio of approximately 60:40 for terephthalic acid units to isophthalic acid units. The product was directly used and marketed by Arkema SA, France, under the commercial name "Kepstan 6002PL".

[0444] The powder used in Example 4 differs from that used in Example 3 in its packing density (the so-called "initial packing density") prior to the method according to the invention. In the case of Example 4, the initial packing density is much lower (0.271 g / cm³). 3 , with 0.318 g / cm 3 compared to).

[0445] The "Henschel FML" model mixer was used again. Except for powder batch number 12, the jacket of the mixer was not cooled. In the case of powder batch number 12, cooling occurred as described in Example 3.

[0446] The method according to the invention was performed ten times using independent powder batches (numbers 11 to 20). The mass of the powder batch is specified as m. The T values ​​for powder batch numbers 11 to 20 are given in Table 8. max T Man The values ​​of m, D1, D2, t1, t2 and t1+t2.

[0447] Table 9 shows the values ​​of the bulk density S obtained. These are the averages of three measurements each. Table 9 also shows the control values ​​for 60:40 PEKK powder that was not treated according to the present invention.

[0448] Table 8

[0449]

[0450] Table 9

[0451]

[0452] exist Figure 6 In the figure, the achieved bulk density is plotted relative to the total processing time t1+t2. Data points where t1+t2=0 represent PEKK powder that was not processed in accordance with the method of the present invention. Figure 6 It is clearly shown that a significant increase in packing density was achieved through the treatment according to the invention. This effect was essentially achieved within a total treatment time of 14 minutes.

[0453] exist Figure 7 The achieved bulk density is plotted relative to residence time t2. The selected data points are displayed. Data points where t2 = 0 indicate PEKK powder that has not been treated according to the method of the present invention. Figure 7 The results show that in many cases, a 10-minute stay leads to the best results.

[0454] The PEKK powder used in Example 4 had a lower initial bulk density (0.271 g / cm³) than the PEKK powder used in Example 3. 3 , with 0.318 g / cm 3 (See the "Comparison" rows in Tables 7 and 9). With a powder mass m = 9 kg in the mixer, the powder used in Example 4 reached a maximum temperature of 99.8°C (temperature of the mixed material) in the mixer when the mixer jacket was cooled by water. Furthermore, in this case, more time was required to reach this maximum temperature T. max Without cooling the mixer jacket, the powder used in Example 4 can be used in the mixer to reach a higher temperature in a shorter time.

[0455] Therefore, the required mixing time in the mixer is strongly dependent on the bulk density of the powder. This is taken into account in the present invention.

[0456] However, even using the powder described in Example 4, the actual maximum increase in bulk density can be achieved with a total processing time of significantly less than 30 minutes, t1+t2. After 26 minutes, 0.35 g / cm³ was reached. 3The platform's packing density did not increase even with longer processing times. The maximum increase in packing density was reached after a total processing time of 15-20 minutes. Thereafter, the packing density increased only slightly.

[0457] Example 5

[0458] In Example 5, PEKK, with a copolymerization ratio of terephthalic acid units to isophthalic acid units of approximately 60:40, was used; it was also used in Examples 3 and 4. Again, the product sold by Arkema SA, France, under the trade name "Kepstan 6002PF" was used. This coarse powder was ground in an impact mill and sieved to the appropriate particle size.

[0459] The "Henschel FML" model mixer was used again. Except for powder batch number 23, the mixer jacket was cooled by water cooling. In the case of powder batch number 23, it was not cooled.

[0460] The method according to the invention was performed three times using independent powder batches (numbers 21 to 23). The mass of the powder batch is specified as m. The T values ​​for batches 21 to 23 are given in Table 10. max The values ​​of m, F, D1, D2, t1, t2, and t1+t2. If no values ​​are entered in the columns and rows, it means that no corresponding measurement was performed.

[0461] The following values ​​obtained are given in Table 11: bulk density S and BET surface area. These are averages from three measurements each. Table 11 also shows control values ​​for 60:40 PEKK powder that was not treated in the manner according to the invention.

[0462] Powders from batches 21, 22, and 23 were each mixed to 1 / 3 by mass and then exposed to 270°C for 2 hours in a circulating air furnace under a nitrogen atmosphere. 270°C roughly corresponds to the start of the melting peak observed in DSC. The bulk density values ​​measured thereafter are also shown in Table 11 (“270°C / 2h”).

[0463] Table 10

[0464]

[0465] Table 11

[0466]

[0467] As can be clearly seen from the values ​​in Table 11, the treatment according to the present invention resulted in a significant increase in bulk density and a significant decrease in BET surface area after a treatment time of significantly less than 30 minutes. At a treatment time of 33 minutes and T... maxAt a value of 165°C, the bulk density is relatively much lower. Even lower BETs are obtained when the powder treated according to the present invention is exposed to a temperature of 270°C for a period of 2 hours.

[0468] Figure 8 The temperature-current consumption graph shows the change in current consumption in the mixer over time compared to the temperature increase of sample number 23. It can be seen that at temperature T... B At a maximum temperature of 150°C, current consumption increases disproportionately by more than 5%.

[0469] As can be seen from the following table representing the temperature-current consumption graph, the current T associated with PEKK 60 / 40 B The maximum value can be at least about 150°C, preferably 154°C, which is due to the respective gradients of about 7% and about 10.5% compared to the corresponding previous values ​​of current consumption.

[0470]

[0471]

[0472] Example 6

[0473] In Example 6, PEKK with a copolymerization ratio of terephthalic acid units to isophthalic acid units of approximately 60:40 was used. The product was sold by Arkema SA, France, under the trade name "Kepstan 6003PF". This coarse powder was ground in an impact mill and sieved to the appropriate particle size.

[0474] The "Henschel FML" model mixer was used again. The jacket of the uncooled mixer was present.

[0475] The method according to the invention was performed using a single powder batch (24). T is given in Table 12. max The values ​​of D1, D2, t1, t2 and t1+t2.

[0476] Table 13 presents the following values ​​obtained: bulk density S, BET surface area, fraction of powder particles with a size <10 μm by volume (% <10 μm), and quantile of particle size distribution d. 10 d 50 and d 90 These are averages from three measurements each. Control values ​​for 60:40 PEKK powder that was not treated according to the method of the invention are also given in Table 13.

[0477] Table 12

[0478]

[0479] Table 13

[0480]

[0481] As can be clearly seen from the values ​​in Table 13, by means of the processing according to the present invention, after a processing time of 17 min, a significant increase in bulk density, a significant decrease in BET surface area, and a significant decrease in the percentage of ultrafine powder (% < 10 μm) can be achieved.

[0482] Example 7

[0483] In Example 7, PEKK with a copolymerization ratio of terephthalic acid units to isophthalic acid units of approximately 60:40 was used. This was similar to the product distributed by Arkema SA, France, under the trade name "Kepstan 6003PF," used in Example 6. The coarse powder was ground in an impact mill and sieved to the appropriate particle size.

[0484] The "Henschel FML" model mixer was used again. The jacket of the uncooled mixer was present.

[0485] The method according to the invention is performed using a single powder batch (number 25). The mass of the powder batch is specified as m. T is given in Table 14. max The values ​​of m, D1, D2, F, t1, t2, and t1+t2.

[0486] Table 15 shows the values ​​of the bulk density S obtained. These are the average values ​​from three measurements. Table 15 also shows the control values ​​for 60:40 PEKK powder that was not treated in the manner according to the invention.

[0487] Table 14

[0488]

[0489] Table 15

[0490]

[0491] As can be clearly seen from the values ​​in Table 15, a significant increase in packing density can be achieved after a processing time of 25 minutes using the processing method according to the present invention.

[0492] Example 8

[0493] In Example 8, PEKK with a copolymerization ratio of terephthalic acid units to isophthalic acid units of approximately 60:40 was used, which contained approximately 36% by weight of carbon fiber as filler (reinforcing material). PEKK powder with carbon fiber bonded in the core, manufactured by ALM LLC, was used.

[0494] The "Henschel FML" model mixer was used again. The jacket of the uncooled mixer was present.

[0495] The method according to the invention was performed using a single powder batch (26). T is given in Table 16. max The values ​​of D1, D2, t1, t2 and t1+t2.

[0496] Table 17 gives the values ​​of the bulk density S obtained. This is the average of three measurements. Table 17 also shows the control values ​​for 60:40 PEKK powder with 36 wt% carbon fiber that was not treated in accordance with the method according to the invention.

[0497] Table 16

[0498]

[0499] Table 17

[0500]

[0501] As can be clearly seen from the values ​​in Table 17, the packing density of carbon fiber reinforced PEKK powder can be significantly improved after a processing time of 16 minutes by the processing according to the present invention.

[0502] In this context, it should be noted that the following applies not only in the context of Example 8 but also generally to fiber-reinforced plastics: for both fiberless and fiber-reinforced PEKK, it has been found experimentally that increases in bulk density can be achieved at similar temperatures. This means that, within the context of this invention, for fiber-reinforced polymers and for other composites of unreinforced polymers, the same or at least similar processing temperatures T are preferred. B .

[0503] Example 9

[0504] In Example 9, the same polyphenylene sulfide (semi-crystalline) powder as in Example 1 ("Toray 50NNAB" from Toray Industries, Inc., Japan) was used. It has a melting point of 293°C and a T... g The temperature was 105℃ (measured according to DIN ENISO 11357) and the MVR (melt viscosity) was 25 cm⁻¹. 3 / 10min (measured by ISO 1133 at 315°C and 2.16kg).

[0505] A "Mixaco LAB-CM 6-12CM / SM" model mixer was used as the mixer. The jacket of the uncooled mixer was also used.

[0506] Below Tg The processing temperature varied between 64-87°C, and the dwell time remained constant at 10 minutes in each case. The heating time varied between 1.5 and 4 minutes.

[0507] Table 18

[0508]

[0509]

[0510] Table 19

[0511]

[0512] In T g Increased packing density can be achieved at temperatures as low as -40°C. At T g -30℃ to T g The increase in bulk density is greatest at a temperature of -19°C.

[0513] Furthermore, the fluidization ability is also significantly improved due to the treatment. Although the powder ground before the treatment according to the invention does not flow freely, it exhibits good fluidization ability after about 4.5 seconds (tested using a 25 mm nozzle), see Table 19.

[0514] As below T g As the processing temperature is continuously increased, BET only decreases slightly, while it remains above T. g (Refer to Example 1, V1-V3, T) B =175℃), BET decreased significantly to approximately 7.5m. 2 / g.

[0515] Furthermore, through the processing according to the invention, the ultrafine powder fraction is significantly reduced from about 0.4% to about 0.3%, see also Table 3.

[0516] Example 10

[0517] Using commercially available Victrex PIC (Thornton Cleveleyses, UK) PEEK150PF semi-crystalline polyetheretherketone (PEEK), with a melting point of 343°C and a T0.05 of 143°C. g .

[0518] A "Mixaco LAB-CM 6-12CM / SM" model mixer was used as the mixer. The jacket of the uncooled mixer was also used.

[0519] The processing temperature varied between 103 and 156°C, and the dwell time remained constant at 10 minutes in each case.

[0520] Table 20

[0521]

[0522] Table 21

[0523]

[0524] In T g The packing density can be increased at a temperature of -40℃, and at T g Further improvements were achieved at a temperature of -11℃. At temperatures above T... g In T g The increase in packing density was greatest at +13 and simultaneously within the range of HDT-A and HDT-B for PEEK (also compared with Table 1).

[0525] BET has also fallen below T. g The temperature decreases with increasing processing temperature; above T g Within the HDT-A and HDT-B ranges, it can be significantly reduced further. It can be inferred that above HDT-B and below T... m At that temperature, BET can decrease further.

[0526] The particle size distribution changes only slightly with increasing processing temperature.

[0527] Research in V3 (T) B =156℃) The current consumption in the mixer increases with the progression of temperature over time, which can Figure 9 As can be seen in Table 22 below. Until T g The current consumption is essentially constant. It can be seen that at T... g Between the HDT-A value and the current consumption, the current consumption increases from 3.0A to 3.4A in the short term. Beyond HDT-A, it decreases to or even exceeds T. g A slightly lower value of 2.8A (2.9-3.0A) indicates better fluidization of the powder, resulting in less shear and consequently lower current consumption. Due to the improved fluidization, the temperature no longer increases further and remains at approximately 156°C despite the same rotational speed. Therefore, the maximum processing temperature for PEEK has not yet reached 156°C. Higher processing temperatures cannot be achieved with this setup because the mixer is already operating at maximum speed during the heating and holding phases.

[0528] However, this can be achieved by using PEEK with a higher initial packing density, different filling levels, or by using a mixer with a higher speed, such as a "Henschel FML" type mixer. The time required for the heating stage can also be significantly reduced.

[0529] Specifically, as can be seen from Table 22, for PEEK 150PF, TB The maximum can be most effectively defined as at most about 150°C (due to a gradient of 12.5% ​​compared to the previous value of current consumption, specifically 149.1°C).

[0530] Table 22

[0531]

[0532] Example 11

[0533] The product used was PEEK-HP3 semi-crystalline polyetheretherketone (PEEK), commercially available from EOS GmbH (Krailling, Germany), which has a melting point of 372°C and a T0.05 of 164°C. g .

[0534] A "Mixaco LAB-CM 6-12CM / SM" model mixer was used as the mixer. The jacket of the uncooled mixer was also used.

[0535] The processing temperature varies between 75-192°C, and the residence time remains constant at 10 minutes in each case. Higher processing temperatures cannot be achieved using this type of mixer, as the highest possible temperature is 200°C.

[0536] Table 23

[0537]

[0538] Table 24

[0539]

[0540] At a temperature of Tg-89℃, only a minimum increase in bulk density of about 1% can be achieved, while at Tg-39℃ and Tg-17℃, significant increases of approximately the same level of 0.48 are achieved. Above Tg and above HDT-A values ​​(compare Table 1), the increase in bulk density is greatest at Tg+27℃.

[0541] BET decreases as the processing temperature increases, and has even fallen below Tg.

[0542] The particle size distribution did not change significantly below the processing temperature (Tg). Above Tg, it increased slightly, which explains the slightly improved fluidization capability.

[0543] For experiment V3(T) B =192℃) The current consumption in the mixer increases with the progression of temperature over time, which can Figure 10As can be seen, up to 114°C, current consumption increases by approximately 10%. Thereafter, it remains essentially constant. Within the range of Tg or HDT-A values, current consumption does not change. Therefore, it is possible to infer that processing temperatures above 192°C and even higher, below Tm, are possible, i.e., until that temperature, current consumption increases significantly and then no longer decreases.

[0544] Example 12

[0545] Using Primecast 101 type amorphous polystyrene, commercially available from EOS GmbH (Krailling, Germany), its T g The temperature is 100℃.

[0546] Use a "Mixaco LAB-CM 6-12CM / SM" model mixer. The jacket of the uncooled mixer is attached.

[0547] For T g The treatment temperature is -2℃, with a holding period of 10 minutes. For the treatment temperature T... g At +16°C, a reasonable holding phase could not be achieved because the powder formed extreme agglomeration in the mixer, making proper mixing impossible. Therefore, the experiment was interrupted after a 2-minute holding phase.

[0548] Table 25

[0549]

[0550] Table 26

[0551]

[0552] As the current consumption in the V2 mixer increases with time and temperature, this can... Figure 11 As shown in Table 27, after the current consumption decreases at the start of the treatment, it remains constant until 111°C (T). g +11), and then a significant increase, which is due to the strong agglomeration that occurs in the mixer.

[0553] Table 27

[0554]

[0555]

[0556] Specifically, as can be seen from Table 27, for polystyrene, T B The maximum can be defined as approximately 113°C (considering a gradient of 6% compared to the previous value of current consumption).

[0557] Example 13

[0558] Polyamide 12 precipitated powder, prepared according to standard procedure EP863174, with a melting point of 187°C, was used. g The temperature is approximately 50°C, and it contains no fluidizing agents. The powder is prepared by precipitation from an ethanol solution. The principle for controlling the particle size distribution and melting point of the starting powder is known from EP863174.

[0559] A "Mixaco LAB-CM 6-12CM / SM" model mixer was used as the mixer. Except in Experiment V10, the jacket of the uncooled mixer was not used.

[0560] In V1 to V3, the processing temperature varied between 56°C and 101°C, while the residence time remained constant at 10 minutes. With increasing temperature, the bulk density increased, reaching a maximum (approximately 4%) at 101.3°C. From processing temperatures above 75.5°C, the ultrafine fraction in V3 decreased significantly from 3.6% to 2.7%.

[0561] During the heating phase (V4 vs. V3), the rotational speed was increased from 23.3 m / s to 34.4 m / s, and the heating time was reduced from 21 min to 15 min. The bulk density remained unchanged, but the fine fraction further decreased from 2.7% to 2.1%.

[0562] In V5-V7, the rotational speed and processing temperature during the heating phase were kept constant at approximately 100°C. Residence time varied between 0 and 30 minutes. Bulk density increased minimally up to 15 minutes, then remained almost constant. The reduction in fine fraction was most significant with no residence time (3.6% to 1.9%), increasing again to 2.2% with longer residence times. Fluidization capacity improved most significantly with a 0-minute residence time up to 6 seconds (minimum free-flow time = optimal fluidization capacity), and increased again to 9 seconds with a 30-minute residence time. From a residence time of 30 minutes onwards, the enthalpy of fusion of the powder and therefore also the crystallinity decreased significantly from 118 to 108 J / g. This indicates that the treatment resulted in melting and recrystallization of the crystalline regions on the surface.

[0563] In experiments V5, V8, and V9, the processing temperature in the mixer varied between 95 and 140 °C, while the rotational speed during the heating phase remained constant at 34.4 m / s and the residence time remained constant at 0 min. At 95 °C and 120 °C, the bulk density increased by more than 2%, decreasing back to the level of the control powder at 140 °C. The ultrafine fraction decreased from 2.7% with increasing processing temperature down to 0.3% at the 140 °C processing temperature.

[0564] In V10, the mixer was cooled; in V11, the mixer was not cooled. The processing temperature remained constant at approximately 125°C during a 30-minute residence time. The revolutions per second (RPM) during the heating phase were 34.4 m / s. Due to mixer cooling, the heating phase was significantly extended from 23 minutes to 48 minutes. The bulk density was slightly higher with the mixer cooled than with the uncooled mixer. Similarly, with mixer cooling, the ultrafine fraction decreased slightly by up to 0.5%, and the fluidization capacity improved slightly by about 7 seconds.

[0565] The change in BET depends on temperature. At a processing temperature of 120°C, regardless of residence time, BET decreases from 5.4 to 3.5 m. 2 / g(V9+V11). At a treatment temperature of 140℃, this even decreases further to approximately 2m. 2 / g.

[0566] With a residence time of 30 minutes, the enthalpy of fusion and consequently the crystallinity decreased significantly from 100 °C (V7, V10, V11). At 120 and 140 °C, the decrease was significant, from 118 J / g to 105 J / g.

[0567] Table 28

[0568]

[0569] Table 29

[0570]

[0571]

[0572] In V9, the study investigated the current consumption of the mixer over time as the temperature increased, which could... Figure 12 As can be seen in Table 30, initially, the current consumption decreases slightly until it reaches approximately Tg. Until the HDT-A temperature is reached (see Table 1), the current consumption increases only very slowly from 3.3 to 3.9 A. From 130.5 °C, the current consumption increases disproportionately sharply from 3.9 A to 4.5 A, an increase of approximately 11%, until it reaches a value of 6.5 A at 140 °C.

[0573] If a residence time (V12) is subsequently applied at 140°C, the temperature continues to rise despite the reduced rotational speed, and after 7 minutes, the current consumption becomes so high that the mixer automatically interrupts the mixing process via a safety shutdown. The bulk density is significantly reduced by approximately 10% compared to the control material.

[0574] Table 30 shows the change in current consumption over time in the mixer for polyamide 12 (without fluidizing agent) as an example, compared to the temperature increase in Experiment V9 of Example 13.

[0575] Table 30

[0576]

[0577]

Claims

1. A method for preparing a powder comprising at least one polymer for use in an additive manufacturing method of a three-dimensional object. Includes the step of mechanically processing the powder in a mixer using at least one rotating mixing blade. Perform at least one heat treatment, wherein the at least one heat treatment includes T on the powder B Heat treatment, the T B Heat treatment is the process of heating powder to a temperature T. B And among them T B Heat treatment simply involves heating the powder to a temperature T. B Heat treatment; If the polymer is a semi-crystalline polymer, then T B At least 30°C and below the polymer's melting point T m According to DIN ENISO 11357, or If the polymer is a molten amorphous polymer, then T B Higher than the glass transition temperature T of the polymer g At least 30°C and at most 50°C, as determined according to DIN EN ISO 11357; Where T B Heat treatment includes: By increasing the heating temperature to limit the heating phase, from below T B The initial temperature begins when mechanical processing of the powder begins, and continues until the heating temperature reaches T. B ;and By heating temperature at T B The retention phase is defined by maintaining it within a range of ±10℃ for a certain period of time. Where T B Determined by one of the following conditions or methods (i) to (iv): (i)T B The temperature above the polymer’s thermal flexural temperature (HDT-A) is determined according to DIN EN ISO 75; measured in standard measurements on a sample consisting solely of the polymer, i.e., without any additives, if the polymer is a semi-crystalline polymer. (ii)T B Below the glass transition temperature T of the polymer g Up to 100°C, as determined according to DIN EN ISO 11357, if the polymer is a semi-crystalline polymer or a molten amorphous polymer; (iii) For the polymer powder to be used, T B At most, the temperature Tmax is the temperature determined in a temperature-current consumption measurement of the same polymer in a mixer with mixing blades rotating in the range of 20 to 50 m / s during heating, wherein Tmax is determined in the temperature-current consumption measurement by one or both of the following methods (a) or (b): (a) Determining the maximum T using a temperature-current consumption graph B One data point is recorded every minute, where only those [(gradient / min) / current consumption] within the range of Tg-20℃ to Tm are considered, which are at least greater than 5% and at most 30%; or (b) Maximum T B The current consumption of the mixer was determined by temperature-current consumption graph, in which the current consumption of the mixer increased disproportionately and strongly to an increased current consumption value lx in a short period of time, which was at least 10% higher than the average of at least 10 previous measurement points, with at least one measurement recorded per minute, wherein only the current increase in the range of Tg-20°C to Tm was considered. (iv)T B It is the temperature Tmax at which the bulk density of the powder decreases to less than that of the untreated powder due to the use of a mixer within ±10°C, where the maximum Tmax is determined by the use of different T... B However, a series of tests were conducted under otherwise identical mixed conditions.

2. The method according to claim 1, Among them, reaching T B Previously, the maximum velocity of the mixing blades during the heating process was at least 20 m / s, and / or Among them, reaching T B Previously, the maximum speed of the mixing blades during the heating process was at most 100 m / s.

3. The method according to claim 1, At least a portion of the powder was from below T B Start at an initial temperature of at least room temperature or at most 60°C above room temperature, and reach temperature T within a heating time of 20 minutes. B .

4. The method according to claim 1, Among them, reaching T B After that, the temperature was maintained at T. B Maintain the dwell time within the range of ±20℃.

5. The method according to claim 1, The polymer is a semi-crystalline polymer and T is present in the polymer. B Above the thermal flexural temperature HDT-A and / or below the thermal flexural temperature HDT-B, and / or wherein the polymer is a semi-crystalline polymer and wherein T B For at least 20°C, and / or The polymer is a semi-crystalline polymer and T is present in the polymer. B For a maximum of 250°C, and / or where the polymer is a semi-crystalline polymer, and where T B Below the glass transition temperature T of the polymer g Up to 50°C, as determined according to DIN EN ISO 11357; or Wherein the polymer is a molten amorphous polymer and where T B Above the glass transition temperature T g At most 20°C and below the glass transition temperature T g At least 10°C, and / or wherein the polymer is a molten amorphous polymer and wherein T B Above the thermal flexural temperature HDT-A, as determined according to DIN EN ISO 75.

6. The method of claim 1, further comprising the step of exposing the powder to temperature T by heating. N A time period of at least 30 minutes and / or at most 30 hours.

7. The method of claim 6, wherein the additional step relates to one or more of the following conditions, each compared with a corresponding parameter value prior to that additional step: Increase bulk density, improve fluidization capacity, reduce BET, increase the onset temperature of melting point and / or increase the enthalpy of fusion of the treated powder.

8. The method according to claim 1, The temperature T at which the powder appears is adjusted in this way. B Compared to the time point before processing began, after processing —The bulk density of the powder is increased by at least 10%, or by at least 2% in the case of polymers, copolymers, or polymer blends of polyamide, and —The BET surface area of ​​the powder is reduced by at least 10%. —Optionally, fluidization capacity is also improved by at least 10%.

9. The method according to claim 1, The polymer is an amorphous, pseudo-amorphous, or semi-crystalline polymer, and one of the following measures is taken: (a) At least two mixing blades are used in the mixer, and the mixing chamber of the mixer has a volume of at least 5 L and at most 100 L; (b) Using at least four mixing blades in a mixer, wherein the mixing chamber of the mixer has a volume of at least 200 L and at most 1000 L; (c) Select a mixer fill level of at least 30% and at most 99%; (d) Temperature T is adjusted by regulating the mixer's rotational speed and the processing duration. B ; (e) The powder reaches temperature T within a maximum of 25 minutes from a lower initial temperature. B Optionally, the temperature is then at T B Maintain within a range of ±20℃ for a period of time.

10. The method according to claim 1, The powder comprises at least one polymer selected from the group consisting of at least two polymers selected from the group consisting of: Polyetherimide, polycarbonate, polyarylene sulfide, polyphenylsulfone, polysulfone, polyphenylene ether, polyethersulfone, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene-acrylate copolymer, polyvinyl chloride, polyacrylate, polyester, polyamide, polyarylene ether ketone, polyether, polyurethane, polyimide, polyamide-imide, polysiloxane, polyolefin and copolymers having at least two different repeating units of the above polymers.

11. The method according to claim 1, The powder comprises at least one polymer selected from the group consisting of at least two polymers selected from the group consisting of: Polyaryletherketone, wherein the polyaryletherketone has a melting point of up to 330°C. m According to DIN EN ISO 11357, and / or wherein the polyaryletherketone has a glass transition temperature T of at least 120°C. g According to DIN EN ISO 11357; Polyetherketoneketone, wherein the polyetherketoneketone has the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at least 40% and at most 80%. Polyether ether ketone or its copolymer with diphenyl ether ketone; Polyetherimide, wherein the polyetherimide comprises repeating units according to the following Formula I , And / or based on the following repeating units Formula II , And / or based on the following repeating units Formula III ; Polycarbonate, wherein the polycarbonate has repeating units according to the following Formula IV ; Polyaryl sulfides, polyphenylene sulfides, which have repeating units according to the following Formula V ; Alternatively, the polymer may be a polymer blend selected from polyaryletherketone-polyetherimide, polyaryletherketone-polyetherimide-polycarbonate, polyphenylene sulfide-polyetherimide, and / or polyetherimide-polycarbonate, optionally wherein the polyaryletherketone of the polymer blend has a terephthalic acid / isophthalic acid isomer ratio between 65 / 35 and 55 / 45, and / or the polyetherimide of the polymer blend comprises repeating units according to Formula I as defined above, and / or wherein the polycarbonate of the polymer blend comprises repeating units according to the following Formula IV Polyphenylene sulfide blends and / or polymer blends have repeating units according to the following Formula V 。 12. The method according to claim 1, wherein a semi-crystalline polyaryletherketone, a semi-crystalline polyphenylene sulfide, or a semi-crystalline polyamide, or a copolymer or polymer blend thereof, is used as the polymer, wherein in this case T B Below the crystallization point Tk, measured according to DIN EN ISO 11357 at a cooling rate of 20 °C / min. Alternatively, pseudo-amorphous polycarbonate, pseudo-amorphous polyetherimide, or pseudo-amorphous polyether ketone ketone, or copolymers or polymer blends thereof, may be used. Alternatively, a molten amorphous polymer can be used, in which case T B Temperatures above the polymer's Tg by up to 20°C, or below the Tg.

13. The method according to claim 1, wherein, The powder is prepared by melt spinning, which includes fiber cutting.

14. A powder comprising at least one polymer for use in an additive manufacturing method for a three-dimensional object. The powder has been obtained by the method defined in claim 1.

15. The powder of claim 14, wherein the powder comprises at least one polymer selected from the polymers and polymer blends defined in any one of claims 10, 11 and 12.

16. The powder according to claim 14, The powder is selected from the following: (i) The powder comprises polyetherketone ketone, wherein the polyetherketone ketone has the following terephthalic acid / isophthalic acid isomer ratio: wherein the molar fraction of terephthalic acid is at least 20% and at most 80%, wherein the powder has: d 90 The value is at most 150 μm, as determined according to ISO 13322-2, and, The bulk density has a minimum of 0.33 g / cm³. 3 The value, The BET surface area of ​​the powder is at most 10 m². 2 / g; (ii) The powder contains polyetherketone ketone and at least 20% by weight of carbon fiber as filler. The powder has the following characteristics: bulk density greater than 0.50 g / cm³. 3 , And / or the BET surface area of ​​the powder therein is at most 10 m² 2 / g; (iii) The powder comprises polyetheretherketone or polyetheretherketone-polyetherdiphenyletherketone copolymer, wherein the powder has: powder d 90 The value is at most 150 μm, determined according to ISO 13322-2, and / or The bulk density is at least 0.32 g / cm³. 3 , and / or The surface area of ​​BET is at most 40 m² 2 / g; (iv) The powder contains polyphenylene sulfide. powder d 90 The value is at most 150 μm, as determined according to ISO 13322-2, and The bulk density has a minimum of 0.48 g / cm³. 3 And / or the BET surface area of ​​the powder is at most 10 m² 2 / g; (v) The powder comprises a polymer blend of polyphenylene sulfide and polyetherimide. The molar fraction of polyphenylene sulfide to polyetherimide is at least 40:60, and Among the powder's d 90 The value is at most 150 μm, as determined according to ISO 13322-2, and the bulk density therein has a minimum of 0.32 g / cm³. 3 The value; (vi) The powder contains polyamide 12, Among the powder's d 90 The value is at most 150 μm, as determined according to ISO 13322-2, and The bulk density has a minimum of 0.35 g / cm³. 3 The value, and / or the surface area of ​​BET is at most 10 m² 2 / g; (vii) The powder contains polyamide 11, Among the powder's d 90 The value is at most 150 μm, as determined according to ISO 13322-2, and The bulk density has a minimum of 0.35 g / cm³. 3 The value, and / or the surface area of ​​BET is at most 10 m² 2 / g; (viii) The powder contains polypropylene. Among the powder's d 90 The value is at most 150 μm, as determined according to ISO 13322-2, and The bulk density has a minimum of 0.36 g / cm³. 3 The value, and / or the surface area of ​​BET is at most 10 m² 2 / g; in, Optionally selected powders according to (i) to (viii) are obtained by melt spinning, which includes fiber cutting.

17. The powder according to claim 14, The powder contains at least one additive selected from the group consisting of: heat stabilizers, oxidation stabilizers, UV stabilizers, fillers, dyes, plasticizers, reinforcing fibers, IR absorbers, and / or flame retardants and flow aids.

18. A method for additive manufacturing of a three-dimensional object, comprising the following steps: Provides the powder as defined in any one of claims 14-17, and Three-dimensional objects are prepared by selectively solidifying powder provided at locations corresponding to the cross-sections of objects in the respective layers using electromagnetic radiation.

Citation Information

Patent Citations

  • Appts. for producing three-dimensional objects by laser sintering

    DE19514740C1

  • Conventional size sample chamber for assembling an ionisation smoke alarm insert

    EP0130558A1

  • Preparation of precipitated polyamide powders with a narrow grain size distribution and low porosity

    EP0863174A1

  • Rounded-particle plastic powder in particular for application in laser sintering, method for production of such a powder and laser sintering process using such a powder

    EP1537170A1

  • Influencing specific mechanical properties of three-dimensional objects manufactured by a selective sintering by means of electromagnetic radiation from a powder comprising at least one polymer or copolymer

    EP2123430A1